Adhesive and method for producing adhesive
By using a combination formula of epoxy resin, polymer particles and non-crosslinked acrylate resin in the adhesive, the shortcomings of existing adhesives in multiple properties are solved, and an optimized peel mode, adhesion and viscosity are achieved.
Patent Information
- Application Number
- JP2021549056
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-09-27
- Filing Date
- 2020-09-25
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2040-09-25
AI Technical Summary
Existing adhesives have shortcomings in adhesion and peeling properties, adhesion and viscosity, and it is difficult to meet multiple performance requirements at the same time.
Adhesive formulations containing epoxy resin (A), polymer particles (B) and non-crosslinked acrylate resin (C) are adopted, where polymer particles include rubber-content fiber particles with elastomers and grafted parts. The non-crosslinked acrylate resin forms a -domain structure after the epoxy resin is cured to improve peeling performance.
The adhesive is optimized in terms of peeling mode, adhesion and viscosity, and the overall performance of the adhesive is improved.
Smart Images

Figure 0007654552000003 
Figure 0007654552000001 
Figure 0007654552000002
Abstract
Description
[Technical field]
[0001] The present invention relates to an adhesive and a method for making an adhesive. [Background technology]
[0002] Conventionally, in various fields, a technique for bonding adherends to each other via an adhesive has been used, and various adhesives have been developed to date. For example, Patent Document 1 discloses a curable composition containing an organic polymer and polymer particles, and also discloses a technique for bonding various substrates to each other using the curable composition (see, for example, Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2018-053026 A Summary of the Invention [Problem to be solved by the invention]
[0004] However, there is room for improvement in the conventional adhesives as described above. In particular, there is a demand for development of adhesives that are excellent in terms of adhesive properties such as peel mode, adhesive strength, and viscosity.
[0005] One aspect of the present invention aims to provide an adhesive with good release mode, adhesive strength and viscosity. [Means for solving the problem]
[0006] As a result of extensive research to solve the above problems, the inventors discovered that an adhesive containing an epoxy resin, polymer microparticles, and a non-crosslinked acrylic resin can achieve an adhesive with good three properties: peel mode, adhesive strength, and viscosity, and thus completed the present invention.
[0007] An adhesive according to one embodiment of the present invention comprises an epoxy resin (A), and 1 to 100 parts by mass of polymer fine particles (B) and 1 to 100 parts by mass of a non-crosslinked acrylic resin (C) relative to 100 parts by mass of the epoxy resin (A), the polymer fine particles (B) comprise a rubber-containing graft copolymer having an elastomer and a graft portion graft-bonded to the elastomer, the elastomer comprises one or more rubbers selected from the group consisting of diene rubbers, (meth)acrylate rubbers, and organosiloxane rubbers, and the graft portion comprises a polymer comprising, as a constituent unit, a constituent unit derived from one or more monomers selected from the group consisting of aromatic vinyl monomers, vinyl cyan monomers, and (meth)acrylate monomers, the adhesive being such that, when the adhesive is cured to obtain a cured product, the non-crosslinked acrylic resin (C) forms domains in the cured product, and the average particle diameter of the polymer fine particles (B) is greater than the major axis of the domains. Effect of the Invention
[0008] According to one aspect of the present invention, an adhesive with good peel mode, adhesive strength, and viscosity can be achieved. [Brief description of the drawings]
[0009] [Figure 1] 1 is an SEM image of the cured product of the adhesive of Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] An embodiment of the present invention will be described below, but the present invention is not limited thereto. The present invention is not limited to each configuration described below, and various modifications are possible within the scope of the claims. In addition, embodiments or examples obtained by appropriately combining the technical means disclosed in different embodiments or examples are also included in the technical scope of the present invention. Furthermore, new technical features can be formed by combining the technical means disclosed in each embodiment. All academic documents and patent documents described in this specification are incorporated herein by reference. In addition, unless otherwise specified in this specification, "A to B" representing a numerical range means "A or more (including A and greater than A) and B or less (including B and smaller than B)".
[0011] 1. Overview of one embodiment of the present invention Adhesives are required to have various properties, and the inventors have come to the conclusion that it is necessary to develop an adhesive that combines a plurality of properties.
[0012] First, one of the important properties of an adhesive is the peel mode. When adherends bonded via an adhesive are peeled from each other (for example, T-peel), (i) a peel mode in which peeling occurs at the interface between the adhesive and the adherend material is called interfacial failure, (ii) a peel mode in which peeling occurs within the adhesive is called cohesive failure, and (iii) a peel mode in which peeling occurs within the adherend material is called material failure. From the viewpoint of adhesive reliability, among these peel modes, cohesive failure is preferred.
[0013] That is, in this specification, the term "adhesive having a good peeling mode" refers to an adhesive whose peeling mode is cohesive failure.
[0014] Next, an important property of an adhesive is its adhesive strength. If the adhesive strength is too weak, the materials to be adhered together cannot be bonded, so an appropriate adhesive strength is required.
[0015] Next, viscosity is an important property of an adhesive. If the viscosity of an adhesive is too high, it becomes difficult to handle the adhesive, so an appropriate viscosity is required for the adhesive.
[0016] One embodiment of the present invention realizes an adhesive that is excellent in all three properties, namely, peel mode, adhesive strength, and viscosity, mentioned above.
[0017] [2. Adhesive] The adhesive according to one embodiment of the present invention contains an epoxy resin (A), and 1 to 100 parts by mass of polymer fine particles (B) and 1 to 100 parts by mass of non-crosslinked acrylic resin (C) per 100 parts by mass of the epoxy resin (A), the polymer fine particles (B) contain a rubber-containing graft copolymer having an elastomer and a graft portion grafted to the elastomer, the elastomer contains at least one selected from the group consisting of diene rubber, (meth)acrylate rubber, and organosiloxane rubber, the graft portion contains a polymer containing a constituent unit derived from at least one monomer selected from the group consisting of aromatic vinyl monomer, vinyl cyan monomer, and (meth)acrylate monomer, when the adhesive is cured to obtain a cured product, the non-crosslinked acrylic resin (C) forms a domain in the cured product, and the average particle diameter of the polymer fine particles (B) is larger than the major axis of the domain. The cured product of the adhesive can also be called an adhesive layer.
[0018] In an adhesive containing an epoxy resin (A) and polymer microparticles (B), the polymer microparticles (B) improve the adhesive strength, but the peeling mode tends to deteriorate. On the other hand, the adhesive according to one embodiment of the present invention has a good peeling mode. The non-crosslinked acrylic resin (C) in the adhesive according to one embodiment of the present invention precipitates as particles after the epoxy resin (A) hardens, and the particles form a sea-island structure in the hardened product. It is believed that the sea-island structure improves the peeling mode of the adhesive. Furthermore, the non-crosslinked acrylic resin (C) has a small effect on the viscosity of the adhesive. Therefore, the adhesive according to one embodiment of the present invention has a good low viscosity.
[0019] The "adhesive according to one embodiment of the present invention" may hereinafter be referred to as "the adhesive".
[0020] (2-1. Epoxy resin (A)) The epoxy resin (A) is not particularly limited as long as it has at least one epoxy group in the molecule.
[0021] As the epoxy resin (A), various epoxy resins can be used, except for the rubber-modified epoxy resin and urethane-modified epoxy resin described below. Specific examples of the epoxy resin (A) include, for example, bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol AD type epoxy resin, bisphenol S type epoxy resin, glycidyl ester type epoxy resin, glycidylamine type epoxy resin, novolac type epoxy resin, glycidyl ether type epoxy resin of bisphenol A propylene oxide adduct, hydrogenated bisphenol A (or F) type epoxy resin, fluorinated epoxy resin, flame-retardant epoxy resin such as glycidyl ether of tetrabromobisphenol A, p-oxybenzoic acid glycidyl ether ester type epoxy resin, m-aminophenol type epoxy resin, diaminodiphenylmethane type epoxy resin, various alicyclic epoxy resins, glycidyl ether of polyhydric alcohol, hydantoin type epoxy resin, epoxidized product of unsaturated polymer such as petroleum resin, and amino-containing glycidyl ether resin.
[0022] Examples of the polyhydric alcohol include N,N-diglycidylaniline, N,N-diglycidyl-o-toluidine, triglycidyl isocyanurate, resorcinol, polyalkylene glycol, and glycerin. Examples of the epoxy resin (A) include epoxy compounds obtained by subjecting the above-mentioned epoxy resin to an addition reaction with bisphenol A (or F) or polybasic acids. The epoxy resin (A) is not limited to these, and any commonly used epoxy resin may be used. These epoxy resins may be used alone or in combination of two or more.
[0023] Among the above-mentioned epoxy resins, those having at least two epoxy groups in one molecule are preferred because they are highly reactive in the curing of the adhesive and the obtained cured product is easy to form a three-dimensional network. Furthermore, as the epoxy resin (A), those having at least two epoxy groups in one molecule, mainly composed of bisphenol type epoxy resin, are preferred because of their excellent economical efficiency and ease of availability. Furthermore, as the epoxy resin (A), hard epoxy resins, that is, epoxy resins having a specific glass transition temperature (Tg), for example, epoxy resins having a Tg of 50°C or higher are preferred.
[0024] Of these epoxy resins (A), bisphenol A type epoxy resins or bisphenol F type epoxy resins are preferred from the viewpoint of advantageous effects such as a high elastic modulus of the resulting cured product, excellent heat resistance and adhesion, and relatively low cost.
[0025] The viscosity of the epoxy resin (A) may be 1,000,000 mPa·s or less, 100,000 mPa·s or less, or 10,000 mPa·s or less at 25° C. According to the above configuration, an adhesive having a low viscosity can be realized.
[0026] (2-2. Polymer fine particles (B)) The polymer fine particles (B) contain a rubber-containing graft copolymer having an elastomer and a graft portion graft-bonded to the elastomer.
[0027] The adhesive contains 1 to 100 parts by mass of polymer fine particles (B), preferably 5 to 50 parts by mass of polymer fine particles (B), and more preferably 5 to 30 parts by mass of polymer fine particles (B), per 100 parts by mass of epoxy resin (A). The more polymer fine particles (B) there are, the more the adhesive strength of the adhesive can be increased.
[0028] (2-2-1. Elastic body) The elastomer contains at least one selected from the group consisting of diene rubber, (meth)acrylate rubber, and organosiloxane rubber. The elastomer may contain natural rubber in addition to the above-mentioned rubber. The elastomer can also be called an elastic portion or rubber particles. In this specification, (meth)acrylate means acrylate and / or methacrylate.
[0029] Hereinafter, the case where the elastomer contains a diene rubber (case A) will be described. In case A, the adhesive obtained can provide an adhesive layer having excellent toughness and impact resistance. An adhesive layer having excellent toughness and / or impact resistance can also be said to be an adhesive layer having excellent durability.
[0030] The diene rubber is an elastomer containing, as a constituent unit, a constituent unit derived from a diene monomer. The diene monomer can also be called a conjugated diene monomer. In case A, the diene rubber may contain, in 100% by weight of the constituent units, 50 to 100% by weight of constituent units derived from diene monomers and 0 to 50% by weight of constituent units derived from vinyl monomers other than diene monomers copolymerizable with the diene monomers. In case A, the diene rubber may contain, as a constituent unit, a constituent unit derived from a (meth)acrylate monomer in an amount less than the constituent units derived from the diene monomers.
[0031] Examples of the diene monomer include 1,3-butadiene, isoprene (2-methyl-1,3-butadiene), 2-chloro-1,3-butadiene, etc. These diene monomers may be used alone or in combination of two or more.
[0032] Examples of vinyl monomers other than diene monomers that can be copolymerized with diene monomers (hereinafter, also referred to as vinyl monomer A) include (a) vinyl arenes such as styrene, α-methylstyrene, monochlorostyrene, and dichlorostyrene; (b) vinyl carboxylic acids such as acrylic acid and methacrylic acid; (c) vinyl cyanides such as acrylonitrile and methacrylonitrile; (d) vinyl halides such as vinyl chloride, vinyl bromide, and chloroprene; (e) vinyl acetate; (f) alkenes such as ethylene, propylene, butylene, and isobutylene; (g) polyfunctional monomers such as diallyl phthalate, triallyl cyanurate, triallyl isocyanurate, and divinylbenzene. The above-mentioned vinyl monomer A may be used alone or in combination of two or more. Among the above-mentioned vinyl monomers A, styrene is particularly preferred.
[0033] In case A, the diene rubber is preferably butadiene rubber (also called polybutadiene rubber) consisting of structural units derived from 1,3-butadiene, or butadiene-styrene rubber (also called polystyrene-butadiene) which is a copolymer of 1,3-butadiene and styrene. The diene rubber is more preferably butadiene rubber. According to the above configuration, the desired effect of the elastomer containing the diene rubber can be more effectively exhibited. In addition, butadiene-styrene rubber is more preferable in that the transparency of the obtained adhesive layer can be increased by adjusting the refractive index.
[0034] Hereinafter, a case where the elastomer contains a (meth)acrylate rubber (case B) will be described. In case B, a wide range of polymer designs for the elastomer are possible by combining a variety of monomers.
[0035] The (meth)acrylate rubber is an elastomer containing, as a structural unit, a structural unit derived from a (meth)acrylate monomer. In case B, the (meth)acrylate rubber may contain, in 100% by weight of structural units, 50 to 100% by weight of structural units derived from a (meth)acrylate monomer, and 0 to 50% by weight of structural units derived from a vinyl monomer other than the (meth)acrylate monomer that is copolymerizable with the (meth)acrylate monomer. In case B, the (meth)acrylate rubber may contain, as a structural unit, a structural unit derived from a diene monomer in an amount less than the structural unit derived from the (meth)acrylate monomer.
[0036] Examples of the (meth)acrylate monomer include: (a) alkyl (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, dodecyl (meth)acrylate, stearyl (meth)acrylate, and behenyl (meth)acrylate; (b) aromatic ring-containing (meth)acrylates such as phenoxyethyl (meth)acrylate and benzyl (meth)acrylate; (c) 2-hydroxyethyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate; hydroxyalkyl (meth)acrylates such as (d) glycidyl (meth)acrylates such as glycidyl (meth)acrylate and glycidyl alkyl (meth)acrylate; (e) alkoxyalkyl (meth)acrylates; (f) allyl alkyl (meth)acrylates such as allyl (meth)acrylate and allyl alkyl (meth)acrylate; (g) polyfunctional (meth)acrylates such as monoethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, and tetraethylene glycol di(meth)acrylate. These (meth)acrylate monomers may be used alone or in combination of two or more. Among these (meth)acrylate monomers, ethyl (meth)acrylate, butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate are preferred, and butyl (meth)acrylate is more preferred.
[0037] In case B, the (meth)acrylate rubber is preferably one or more selected from the group consisting of ethyl (meth)acrylate rubber, butyl (meth)acrylate rubber, and 2-ethylhexyl (meth)acrylate rubber, and more preferably butyl (meth)acrylate rubber. The ethyl (meth)acrylate rubber is a rubber consisting of structural units derived from ethyl (meth)acrylate, the butyl (meth)acrylate rubber is a rubber consisting of structural units derived from butyl (meth)acrylate, and the 2-ethylhexyl (meth)acrylate rubber is a rubber consisting of structural units derived from 2-ethylhexyl (meth)acrylate. According to this configuration, the glass transition temperature (Tg) of the elastomer is lowered, and therefore the glass transition temperature (Tg) of the polymer microparticles (B) containing the elastomer is also lowered. As a result, (a) the obtained adhesive can provide an adhesive layer having excellent toughness, and (b) the viscosity of the adhesive can be further lowered.
[0038] Examples of vinyl monomers other than (meth)acrylate monomers that are copolymerizable with (meth)acrylate monomers (hereinafter also referred to as vinyl monomer B) include the monomers listed as vinyl monomer A. The vinyl monomer B may be used alone or in combination of two or more. Among the vinyl monomers B, styrene is particularly preferred.
[0039] The case where the elastic body contains an organosiloxane rubber (Case C) will be described below. In Case C, the adhesive obtained has sufficient heat resistance and can provide an adhesive layer that has excellent impact resistance at low temperatures.
[0040] Examples of organosiloxane rubbers include (a) organosiloxane polymers composed of alkyl or aryl disubstituted silyloxy units, such as dimethylsilyloxy, diethylsilyloxy, methylphenylsilyloxy, diphenylsilyloxy, and dimethylsilyloxy-diphenylsilyloxy, and (b) organosiloxane polymers composed of alkyl or aryl monosubstituted silyloxy units, such as organohydrogensilyloxy in which a portion of the alkyl in the side chain is replaced with a hydrogen atom. These organosiloxane polymers may be used alone or in combination of two or more.
[0041] In this specification, a polymer composed of dimethylsilyloxy units is referred to as dimethylsilyloxy rubber, a polymer composed of methylphenylsilyloxy units is referred to as methylphenylsilyloxy rubber, and a polymer composed of dimethylsilyloxy units and diphenylsilyloxy units is referred to as dimethylsilyloxy-diphenylsilyloxy rubber. In case C, the organosiloxane rubber is preferably one or more selected from the group consisting of dimethylsilyloxy rubber, methylphenylsilyloxy rubber, and dimethylsilyloxy-diphenylsilyloxy rubber, (a) because the resulting adhesive can provide an adhesive layer having excellent heat resistance, and (b) because it is easily available and economical, dimethylsilyloxy rubber is more preferable.
[0042] In case C, the polymer fine particles (B) preferably contain 80% by weight or more, and more preferably 90% by weight or more, of the organosiloxane rubber based on 100% by weight of the elastomer contained in the polymer fine particles (B). According to the above-mentioned constitution, the obtained adhesive can provide an adhesive layer having excellent heat resistance.
[0043] In one embodiment of the present invention, the elastomer is preferably one or more selected from the group consisting of butadiene rubber, butadiene-styrene rubber, butadiene-(meth)acrylate rubber, ethyl (meth)acrylate rubber, butyl (meth)acrylate rubber, 2-ethylhexyl (meth)acrylate rubber, dimethylsilyloxy rubber, methylphenylsilyloxy rubber, and dimethylsilyloxy-diphenylsilyloxy rubber, and more preferably one or more selected from the group consisting of butadiene rubber, butadiene-styrene rubber, butyl (meth)acrylate rubber, and dimethylsilyloxy rubber.
[0044] (Elastomeric bridge structure) Since the dispersion stability of the polymer fine particles (B) in the epoxy resin (A) can be maintained, it is preferable that a crosslinked structure is introduced into the elastomer. A commonly used method can be adopted as a method for introducing a crosslinked structure into the elastomer, and examples thereof include the following methods. That is, in the production of the elastomer, a method in which a crosslinkable monomer such as a multifunctional monomer and / or a mercapto group-containing compound is mixed with a monomer capable of constituting the elastomer, and then polymerized, can be mentioned. In this specification, the production of a polymer such as an elastomer is also referred to as polymerizing a polymer.
[0045] Methods for introducing a crosslinked structure into organosiloxane rubber include the following: (a) a method of using a polyfunctional alkoxysilane compound in combination with other materials when polymerizing organosiloxane rubber; (b) a method of introducing reactive groups (e.g., (a) mercapto groups and (b) reactive vinyl groups, etc.) into organosiloxane rubber, and then adding (a) an organic peroxide or (b) a polymerizable vinyl monomer, etc. to the resulting reaction product to cause a radical reaction; and (c) a method of mixing a crosslinkable monomer such as a polyfunctional monomer and / or a mercapto group-containing compound with other materials when polymerizing organosiloxane rubber, and then polymerizing the rubber.
[0046] A polyfunctional monomer can be said to be a monomer having two or more radically polymerizable reactive groups in the same molecule. The radically polymerizable reactive group is preferably a carbon-carbon double bond. Examples of polyfunctional monomers include (meth)acrylates having ethylenically unsaturated double bonds, such as allyl alkyl (meth)acrylates and allyloxy alkyl (meth)acrylates, and do not include butadiene. Examples of monomers having two (meth)acrylic groups include ethylene glycol di(meth)acrylate, butylene glycol di(meth)acrylate, butane diol di(meth)acrylate, hexane diol di(meth)acrylate, cyclohexane dimethanol di(meth)acrylate, and polyethylene glycol di(meth)acrylates. Examples of the polyethylene glycol di(meth)acrylates include triethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, and polyethylene glycol (600) di(meth)acrylate. Examples of monomers having three (meth)acrylic groups include alkoxylated trimethylolpropane tri(meth)acrylates, glycerol propoxy tri(meth)acrylate, pentaerythritol tri(meth)acrylate, and tris(2-hydroxyethyl)isocyanurate tri(meth)acrylate. Examples of the alkoxylated trimethylolpropane tri(meth)acrylates include trimethylolpropane tri(meth)acrylate and trimethylolpropane triethoxy tri(meth)acrylate. Further, examples of monomers having four (meth)acrylic groups include pentaerythritol tetra(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, etc. Further, examples of monomers having five (meth)acrylic groups include dipentaerythritol penta(meth)acrylate, etc. Further, examples of monomers having six (meth)acrylic groups include ditrimethylolpropane hexa(meth)acrylate, etc.Polyfunctional monomers also include diallyl phthalate, triallyl cyanurate, triallyl isocyanurate, divinylbenzene, and the like.
[0047] Examples of the mercapto group-containing compound include alkyl group-substituted mercaptans, allyl group-substituted mercaptans, aryl group-substituted mercaptans, hydroxy group-substituted mercaptans, alkoxy group-substituted mercaptans, cyano group-substituted mercaptans, amino group-substituted mercaptans, silyl group-substituted mercaptans, acid group-substituted mercaptans, halo group-substituted mercaptans, and acyl group-substituted mercaptans. The alkyl group-substituted mercaptans are preferably alkyl group-substituted mercaptans having 1 to 20 carbon atoms, and more preferably alkyl group-substituted mercaptans having 1 to 10 carbon atoms. The aryl group-substituted mercaptans are preferably phenyl group-substituted mercaptans. The alkoxy group-substituted mercaptans are preferably alkoxy group-substituted mercaptans having 1 to 20 carbon atoms, and more preferably alkoxy group-substituted mercaptans having 1 to 10 carbon atoms. The acid group-substituted mercaptan is preferably an alkyl group-substituted mercaptan having 1 to 10 carbon atoms and a carboxyl group, or an aryl group-substituted mercaptan having 1 to 12 carbon atoms and a carboxyl group.
[0048] (Glass transition temperature of elastic body) The glass transition temperature of the elastic body is preferably 80°C or lower, more preferably 70°C or lower, more preferably 60°C or lower, more preferably 50°C or lower, more preferably 40°C or lower, more preferably 30°C or lower, more preferably 20°C or lower, more preferably 10°C or lower, more preferably 0°C or lower, more preferably -20°C or lower, more preferably -40°C or lower, more preferably -45°C or lower, more preferably -50°C or lower, more preferably -55°C or lower, more preferably -60°C or lower, more preferably -65°C or lower, more preferably -70°C or lower, more preferably -75°C or lower, more preferably -80°C or lower, more preferably -85°C or lower, more preferably -90°C or lower, more preferably -95°C or lower, more preferably -100°C or lower, more preferably -105°C or lower, more preferably -110°C or lower, more preferably -115°C or lower, even more preferably -120°C or lower, and particularly preferably -125°C or lower. In this specification, "glass transition temperature" may be referred to as "Tg". According to this configuration, it is possible to obtain polymer fine particles (B) having a low glass transition temperature (Tg) and an adhesive having a low glass transition temperature (Tg). As a result, the adhesive can provide an adhesive layer having excellent toughness. Furthermore, according to this configuration, it is possible to further reduce the viscosity of the adhesive. The Tg of the elastic body can be obtained by performing viscoelasticity measurement using a flat plate made of polymer fine particles (B). Specifically, the Tg can be measured as follows: (1) A dynamic viscoelasticity measurement is performed under tensile conditions on a flat plate made of polymer fine particles (B) using a dynamic viscoelasticity measuring device (e.g., DVA-200, manufactured by IT Measurement and Control Co., Ltd.) to obtain a tan δ graph; (2) The peak temperature of tan δ in the obtained tan δ graph is taken as the glass transition temperature. Here, when multiple peaks are obtained in the tan δ graph, the lowest peak temperature is taken as the glass transition temperature of the elastic body.
[0049] On the other hand, since this can suppress a decrease in the elastic modulus (rigidity) of the resulting cured product, i.e., a cured product having sufficient elastic modulus (rigidity) can be obtained, the Tg of the elastomer is preferably greater than 0°C, more preferably 20°C or higher, even more preferably 50°C or higher, particularly preferably 80°C or higher, and most preferably 120°C or higher.
[0050] The Tg of the elastomer can be determined by the composition of the structural units contained in the elastomer, etc. In other words, the Tg of the resulting elastomer can be adjusted by changing the composition of the monomers used when producing (polymerizing) the elastomer.
[0051] Here, when a homopolymer is formed by polymerizing only one type of monomer, a group of monomers that provides a homopolymer having a Tg greater than 0°C is referred to as monomer group a. When a homopolymer is formed by polymerizing only one type of monomer, a group of monomers that provides a homopolymer having a Tg less than 0°C is referred to as monomer group b. An elastomer containing 50 to 100% by weight (more preferably 65 to 99% by weight) of a constituent unit derived from at least one monomer selected from monomer group a and 0 to 50% by weight (more preferably 1 to 35% by weight) of a constituent unit derived from at least one monomer selected from monomer group b is referred to as elastomer X. The elastomer X has a Tg greater than 0°C. When the elastomer contains elastomer X, the resulting adhesive can provide an adhesive layer having sufficient rigidity.
[0052] It is preferable that a crosslinked structure is introduced into the elastomer even when the Tg of the elastomer is higher than 0° C. Methods for introducing a crosslinked structure include the methods described above.
[0053] Examples of monomers that may be included in the monomer group a include, but are not limited to, unsubstituted vinyl aromatic compounds such as styrene and 2-vinylnaphthalene; vinyl substituted aromatic compounds such as α-methylstyrene; ring-alkylated vinyl aromatic compounds such as 3-methylstyrene, 4-methylstyrene, 2,4-dimethylstyrene, 2,5-dimethylstyrene, 3,5-dimethylstyrene, and 2,4,6-trimethylstyrene; ring-alkoxylated vinyl aromatic compounds such as 4-methoxystyrene and 4-ethoxystyrene; ring-halogenated vinyl aromatic compounds such as 2-chlorostyrene and 3-chlorostyrene; ring-ester substituted vinyl aromatic compounds such as 4-acetoxystyrene; ring-hydroxylated vinyl aromatic compounds such as 4-hydroxystyrene. vinyl esters such as vinyl benzoate and vinyl cyclohexanoate; vinyl halides such as vinyl chloride; aromatic monomers such as acenaphthalene and indene; alkyl methacrylates such as methyl methacrylate, ethyl methacrylate and isopropyl methacrylate; aromatic methacrylates such as phenyl methacrylate; methacrylates such as isobornyl methacrylate and trimethylsilyl methacrylate; methacrylic monomers including methacrylic acid derivatives such as methacrylonitrile; certain acrylic acid esters such as isobornyl acrylate and tert-butyl acrylate; acrylic monomers including acrylic acid derivatives such as acrylonitrile, and the like. Further, examples of monomers that may be included in the monomer group a include acrylamide, isopropylacrylamide, N-vinylpyrrolidone, isobornyl methacrylate, dicyclopentanyl methacrylate, 2-methyl-2-adamantyl methacrylate, 1-adamantyl acrylate, 1-adamantyl methacrylate, etc., which, when made into a homopolymer, can provide a homopolymer having a Tg of 120° C. or higher. These monomers a may be used alone or in combination of two or more kinds.
[0054] Examples of the monomer b include ethyl acrylate, butyl acrylate (also known as butyl acrylate), 2-ethylhexyl acrylate, octyl (meth)acrylate, dodecyl (meth)acrylate, 2-hydroxyethyl acrylate, and 4-hydroxybutyl acrylate. These monomers b may be used alone or in combination of two or more. Among these monomers b, ethyl acrylate, butyl acrylate, and 2-ethylhexyl acrylate are particularly preferred.
[0055] (Volume average particle size of elastic body) The volume average particle diameter of the elastomer is preferably 0.03 μm to 50.00 μm, more preferably 0.05 μm to 10.00 μm, more preferably 0.08 μm to 2.00 μm, even more preferably 0.10 μm to 1.00 μm, even more preferably 0.10 μm to 0.80 μm, and particularly preferably 0.10 μm to 0.50 μm. When the volume average particle diameter of the elastomer is (a) 0.03 μm or more, an elastomer having a desired volume average particle diameter can be stably obtained, and when it is (b) 50.00 μm or less, the heat resistance and impact resistance of the obtained adhesive layer become good. The volume average particle diameter of the elastomer can be measured using a dynamic light scattering particle size distribution measuring device or the like, using an aqueous latex containing the elastomer as a sample.
[0056] (Ratio of elastic body) The proportion of the elastomer in the polymer microparticles (B) is preferably 40 to 97% by weight, more preferably 60 to 95% by weight, and even more preferably 70 to 93% by weight, based on 100% by weight of the entire polymer microparticles (B). When the proportion of the elastomer is 40% by weight or more, the resulting adhesive can provide a cured product having excellent toughness and impact resistance. When the proportion of the elastomer is 97% by weight or less, the polymer microparticles (B) do not easily aggregate (are unlikely to aggregate), so the resulting adhesive does not become highly viscous. As a result, the adhesive can be easy to handle.
[0057] (gel content of elastomer) The elastomer is preferably one that can swell in a suitable solvent but is not substantially soluble in the solvent, and is preferably insoluble in the epoxy resin (A) used.
[0058] The elastomer preferably has a gel content of 60% by weight or more, more preferably 80% by weight or more, even more preferably 90% by weight or more, and particularly preferably 95% by weight or more. When the gel content of the elastomer is within the above range, the resulting adhesive can provide an adhesive layer with excellent toughness.
[0059] In this specification, the method of calculating the gel content is as follows. First, an aqueous latex containing polymer fine particles (B) is obtained, and then a powder of polymer fine particles (B) is obtained from the aqueous latex. The method of obtaining the powder of polymer fine particles (B) from the aqueous latex is not particularly limited, but for example, there is a method of (i) agglomerating the polymer fine particles (B) in the aqueous latex, (ii) dehydrating the obtained agglomerate, and (iii) further drying the agglomerate to obtain a powder of polymer fine particles (B). Next, 2.0 g of the powder of polymer fine particles (B) is dissolved in 50 mL of methyl ethyl ketone (MEK). Then, the obtained MEK solution is separated into a component soluble in MEK (MEK soluble component) and a component insoluble in MEK (MEK insoluble component). Specifically, the obtained MEK soluble matter is centrifuged at 30,000 rpm for 1 hour using a centrifuge (CP60E, manufactured by Hitachi Koki Co., Ltd.), and the soluble matter is separated into MEK soluble matter and MEK insoluble matter. A total of three sets of centrifugation are performed. The weights of the obtained MEK soluble matter and MEK insoluble matter are measured, and the gel content is calculated using the following formula. Gel content (%)=(weight of methyl ethyl ketone insoluble matter) / {(weight of methyl ethyl ketone insoluble matter)+(weight of methyl ethyl ketone soluble matter)}×100.
[0060] (Deformation of Elastic Body) In one embodiment of the present invention, the "elastic body" of the polymer fine particles (B) may be composed of only one type of elastomer having the same composition of structural units. In this case, the "elastic body" of the polymer fine particles (B) is one type selected from the group consisting of diene rubbers, (meth)acrylate rubbers, and organosiloxane rubbers.
[0061] In one embodiment of the present invention, the "elastic body" of the polymer microparticles (B) may be composed of a plurality of types of elastomers having different compositions of constituent units. In this case, the "elastic body" of the polymer microparticles (B) may be two or more types selected from the group consisting of diene rubber, (meth)acrylate rubber, and organosiloxane rubber. In addition, in this case, the "elastic body" of the polymer microparticles (B) may be one type selected from the group consisting of diene rubber, (meth)acrylate rubber, and organosiloxane rubber. In other words, the "elastic body" of the polymer microparticles (B) may be a plurality of types of diene rubber, (meth)acrylate rubber, or organosiloxane rubber having different compositions of constituent units.
[0062] In one embodiment of the present invention, the "elastic body" of the polymer fine particles (B) is described as being composed of a plurality of types of elastomers each having a different composition of constituent units. In this case, the plurality of types of elastomers are referred to as elastomer 1, elastomer 2, ..., and elastomer n Here, n is an integer of 2 or more. The "elastic body" of the polymer microparticle (B) is composed of elastomer 1, elastomer 2, ..., and elastomer 3, which are polymerized separately. n The "elastic body" of the polymer fine particles (B) may include elastomer 1, elastomer 2, ..., and elastomer n may include one elastomer obtained by sequentially polymerizing each of the above. Such sequential polymerization of a plurality of elastomers (polymers) is also called multi-stage polymerization. One elastomer obtained by multi-stage polymerization of a plurality of types of elastomers is also called a multi-stage polymerized elastomer. The method for producing the multi-stage polymerized elastomer will be described in detail later.
[0063] Elastic body 1, Elastic body 2, ..., and Elastic bodyn In the multi-stage polymerized elastomer, n is an elastic body n-1 or an elastic body. n-1 In the multi-stage polymerized elastomer, n Part of the material is elastic. n-1 Sometimes it penetrates inside the
[0064] In the multistage polymerized elastomer, each of the multiple elastomers may form a layer structure. For example, when the multistage polymerized elastomer is composed of elastomer 1, elastomer 2, and elastomer 3, an embodiment in which elastomer 1 forms the innermost layer, a layer of elastomer 2 is formed outside of elastomer 1, and a layer of elastomer 3 is further formed outside of the layer of elastomer 2 as the outermost layer of the elastomer is also one aspect of the present invention. In this way, a multistage polymerized elastomer in which each of the multiple elastomers forms a layer structure can also be called a multilayer elastomer. That is, in one embodiment of the present invention, the "elastic body" of the polymer microparticle (B) may include (a) a composite of multiple types of elastomers, (b) a multistage polymerized elastomer, and / or (c) a multilayer elastomer.
[0065] (2-2-2. Graft part) In this specification, the polymer grafted to the elastomer is referred to as the graft portion. The graft portion includes a polymer containing, as a constituent unit, a constituent unit derived from one or more monomers selected from the group consisting of an aromatic vinyl monomer, a vinylcyan monomer, and a (meth)acrylate monomer.
[0066] The graft portion has the above-mentioned structure and can therefore fulfill various roles, such as (a) improving the compatibility between the epoxy resin (A) and the polymer fine particles (B), (b) improving the dispersibility of the polymer fine particles (B) in the epoxy resin (A), and (c) enabling the polymer fine particles (B) to be dispersed in the adhesive or cured product in the form of primary particles.
[0067] Specific examples of aromatic vinyl monomers include styrene, α-methylstyrene, p-methylstyrene, and divinylbenzene.
[0068] Specific examples of vinyl cyanide monomers include acrylonitrile and methacrylonitrile.
[0069] Specific examples of the (meth)acrylate monomer include methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, hydroxyethyl (meth)acrylate, and hydroxybutyl (meth)acrylate.
[0070] The one or more monomers selected from the group consisting of the aromatic vinyl monomer, the vinyl cyan monomer, and the (meth)acrylate monomer may be used alone or in combination of two or more.
[0071] The graft portion preferably contains, as structural units, structural units derived from an aromatic vinyl monomer, structural units derived from a vinyl cyan monomer, and structural units derived from a (meth)acrylate monomer in a total amount of 10 to 95% by weight, more preferably 30 to 92% by weight, even more preferably 50 to 90% by weight, particularly preferably 60 to 87% by weight, and most preferably 70 to 85% by weight, based on 100% by weight of all structural units.
[0072] The graft portion preferably contains, as a constituent unit, a constituent unit derived from a monomer having a reactive group. The monomer having a reactive group is preferably a monomer having one or more reactive groups selected from the group consisting of an epoxy group, an oxetane group, a hydroxyl group, an amino group, an imide group, a carboxylic acid group, a carboxylic anhydride group, a cyclic ester, a cyclic amide, a benzoxazine group, and a cyanate ester group, more preferably a monomer having one or more reactive groups selected from the group consisting of an epoxy group, a hydroxyl group, and a carboxylic acid group, and most preferably a monomer having an epoxy group. According to the above configuration, the graft portion of the polymer fine particles (B) can be chemically bonded to the epoxy resin (A) in the adhesive. This allows the polymer fine particles (B) to be maintained in a good dispersed state in the adhesive or in the adhesive layer of the adhesive without agglomerating the polymer fine particles (B).
[0073] Specific examples of monomers having an epoxy group include glycidyl group-containing vinyl monomers such as glycidyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate glycidyl ether, and allyl glycidyl ether.
[0074] Specific examples of monomers having a hydroxyl group include, for example, (a) hydroxy linear alkyl (meth)acrylates (particularly, hydroxy linear C1-6 alkyl (meth)acrylates) such as 2-hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate; (b) caprolactone-modified hydroxy (meth)acrylates; (c) hydroxy branched alkyl (meth)acrylates such as α-(hydroxymethyl)methyl acrylate and α-(hydroxymethyl)ethyl acrylate; and (d) hydroxyl group-containing (meth)acrylates such as mono(meth)acrylates of polyester diols (particularly saturated polyester diols) obtained from divalent carboxylic acids (such as phthalic acid) and dihydric alcohols (such as propylene glycol).
[0075] Specific examples of the monomer having a carboxylic acid group include monocarboxylic acids such as acrylic acid, methacrylic acid, and crotonic acid, and dicarboxylic acids such as maleic acid, fumaric acid, and itaconic acid. As the monomer having a carboxylic acid group, the above-mentioned monocarboxylic acids are preferably used.
[0076] The above-mentioned monomers having a reactive group may be used alone or in combination of two or more kinds.
[0077] The graft portion preferably contains 0.5 to 90% by weight, more preferably 1 to 50% by weight, even more preferably 2 to 35% by weight, and particularly preferably 3 to 20% by weight of a structural unit derived from a monomer having a reactive group, based on 100% by weight of the graft portion. When the graft portion contains 0.5% by weight or more of a structural unit derived from a monomer having a reactive group, based on 100% by weight of the graft portion, the resulting adhesive can provide a cured product having sufficient impact resistance. When the graft portion contains 90% by weight or less of a structural unit derived from a monomer having a reactive group, based on 100% by weight of the graft portion, the resulting adhesive can provide a cured product having sufficient impact resistance, and has the advantage of having good storage stability.
[0078] The structural unit derived from a monomer having a reactive group is preferably contained in the graft portion, and more preferably contained only in the graft portion.
[0079] The graft portion may contain a constituent unit derived from a polyfunctional monomer as a constituent unit. When the graft portion contains a constituent unit derived from a polyfunctional monomer, it has the following advantages: (a) swelling of the polymer fine particles (B) in the adhesive can be prevented, (b) the adhesive has a low viscosity, which tends to improve the handleability of the adhesive, and (c) the dispersibility of the polymer fine particles (B) in the epoxy resin (A) is improved.
[0080] When the graft portion does not contain a structural unit derived from a polyfunctional monomer, the resulting adhesive can provide a cured product that is more excellent in toughness and impact resistance, compared to when the graft portion contains a structural unit derived from a polyfunctional monomer.
[0081] The polyfunctional monomers that can be used for the polymerization of the graft portion include the same monomers as the polyfunctional monomers described above. Among these polyfunctional monomers, the polyfunctional monomers that can be preferably used for the polymerization of the graft portion include allyl methacrylate, butylene glycol di(meth)acrylate, ethylene glycol di(meth)acrylate, butanediol di(meth)acrylate, hexanediol di(meth)acrylate, cyclohexanedimethanol di(meth)acrylate, and polyethylene glycol di(meth)acrylates. These polyfunctional monomers may be used alone or in combination of two or more.
[0082] The graft portion preferably contains 1 to 20% by weight, and more preferably 5 to 15% by weight, of structural units derived from polyfunctional monomers, based on 100% by weight of the graft portion.
[0083] In the polymerization of the graft portion, the above-mentioned monomers may be used alone or in combination of two or more.
[0084] The graft portion may contain, as a structural unit, a structural unit derived from another monomer in addition to the structural units derived from the above-mentioned monomers.
[0085] (Glass transition temperature of grafted part) The glass transition temperature of the graft portion is preferably 190°C or less, more preferably 160°C or less, more preferably 140°C or less, more preferably 120°C or less, more preferably 80°C or less, more preferably 70°C or less, more preferably 60°C or less, more preferably 50°C or less, more preferably 40°C or less, more preferably 30°C or less, more preferably 20°C or less, more preferably 10°C or less, more preferably 0°C or less, more preferably -20°C or less, more preferably -40°C or less, more preferably -45°C or less, more preferably -50°C or less. °C or less, more preferably -55°C or less, more preferably -60°C or less, more preferably -65°C or less, more preferably -70°C or less, more preferably -75°C or less, more preferably -80°C or less, more preferably -85°C or less, more preferably -90°C or less, more preferably -95°C or less, more preferably -100°C or less, more preferably -105°C or less, more preferably -110°C or less, more preferably -115°C or less, even more preferably -120°C or less, and particularly preferably -125°C or less.
[0086] The glass transition temperature of the graft portion is preferably 0°C or higher, more preferably 30°C or higher, more preferably 50°C or higher, more preferably 70°C or higher, even more preferably 90°C or higher, and particularly preferably 110°C or lower.
[0087] The Tg of the graft portion can be determined by the composition of the structural units contained in the graft portion, etc. In other words, the Tg of the resulting graft portion can be adjusted by changing the composition of the monomers used when producing (polymerizing) the graft portion.
[0088] The Tg of the graft portion can be obtained by performing viscoelasticity measurement using a flat plate made of polymer microparticles. Specifically, the Tg can be measured as follows: (1) A dynamic viscoelasticity measurement is performed under tensile conditions on a flat plate made of polymer microparticles using a dynamic viscoelasticity measuring device (e.g., DVA-200, manufactured by IT Measurement & Control Co., Ltd.) to obtain a tan δ graph; (2) The peak temperature of tan δ in the obtained tan δ graph is taken as the glass transition temperature. Here, when multiple peaks are obtained in the tan δ graph, the highest peak temperature is taken as the glass transition temperature of the graft portion.
[0089] (Graft ratio of grafted part) In one embodiment of the present invention, in the process of producing the polymer fine particles (B), a polymer having the same structure as the graft portion and not grafted to the elastomer (also called a non-graft polymer) may be generated. The polymer may have the same structure as the non-crosslinked acrylic resin (C) or a different structure.
[0090] When the polymer (non-grafted polymer) has the same structure as the non-crosslinked acrylic resin (C), the non-crosslinked acrylic resin (C) contained in the adhesive according to one embodiment of the present invention may be (i) derived only from the polymer, or (ii) a mixture of the polymer and a polymer (non-grafted polymer) having a different origin from the polymer.
[0091] When the polymer (non-grafted polymer) has a structure different from that of the non-crosslinked acrylic resin (C), the polymer can be regarded as constituting a part of the polymer microparticles (B) according to one embodiment of the present invention. On the other hand, when the polymer (non-grafted polymer) has the same structure as that of the non-crosslinked acrylic resin (C), the polymer is not regarded as constituting a part of the polymer microparticles (B) according to one embodiment of the present invention.
[0092] In this specification, the ratio of the polymer grafted to the elastomer, i.e., the ratio of the grafted portion, among the polymers produced in the polymerization of the grafted portion, is referred to as the graft ratio. The graft ratio can also be expressed as the value expressed by (weight of the grafted portion) / {(weight of the grafted portion)+(weight of the non-grafted polymer)}×100.
[0093] The graft ratio of the graft portion is preferably 70% or more, more preferably 80% or more, and even more preferably 90% or more. When the graft ratio is 70% or more, there is an advantage that the viscosity of the adhesive does not become too high.
[0094] In this specification, the graft ratio is calculated as follows. First, an aqueous latex containing polymer fine particles (B) is obtained, and then a powder of polymer fine particles (B) is obtained from the aqueous latex. A specific method for obtaining a powder of polymer fine particles (B) from an aqueous latex includes (i) coagulating the polymer fine particles (B) in the aqueous latex, (ii) dehydrating the obtained coagulated material, and (iii) further drying the coagulated material to obtain a powder of polymer fine particles (B). Next, 2 g of the powder of polymer fine particles (B) is dissolved in 50 mL of methyl ethyl ketone (MEK). Then, the obtained MEK solution is separated into a component soluble in MEK (MEK soluble content) and a component insoluble in MEK (MEK insoluble content). Specifically, the obtained MEK soluble matter is centrifuged at 30,000 rpm for 1 hour using a centrifuge (CP60E, manufactured by Hitachi Koki Co., Ltd.), and the soluble matter is separated into MEK soluble matter and MEK insoluble matter. Here, a total of three sets of centrifugation are performed. Next, 20 ml of the concentrated MEK soluble matter is mixed with 200 ml of methanol. An aqueous calcium chloride solution prepared by dissolving 0.01 g of calcium chloride in water is added to the obtained mixture, and the obtained mixture is stirred for 1 hour. Thereafter, the obtained mixture is separated into methanol soluble matter and methanol insoluble matter, and the weight of the methanol insoluble matter is taken as the amount of free polymer (FP).
[0095] The graft ratio is calculated according to the following formula. Graft rate (%) = 100 - [(FP amount) / {(FP amount)+(weight of MEK insoluble matter)}] / (weight of polymer in grafted portion) x 10,000.
[0096] The weight of the polymer other than the graft portion is the charged amount of the monomer constituting the polymer other than the graft portion. The polymer other than the graft portion is, for example, an elastomer. When the polymer fine particles (B) contain a surface cross-linked polymer described later, the polymer other than the graft portion includes both an elastomer and a surface cross-linked polymer. The weight of the polymer of the graft portion is the charged amount of the monomer constituting the polymer of the graft portion. In addition, in calculating the graft ratio, the method of coagulating the polymer fine particles (B) is not particularly limited, and a method using a solvent, a method using a coagulant, a method spraying an aqueous latex, etc. may be used.
[0097] (Modification of the graft part) In one embodiment of the present invention, the graft portion may be composed of only one type of graft portion having structural units of the same composition. In one embodiment of the present invention, the graft portion may be composed of multiple types of graft portions each having a structural unit of a different composition.
[0098] In one embodiment of the present invention, a case where the graft portion is composed of a plurality of types of graft portions will be described. In this case, each of the plurality of types of graft portions will be referred to as graft portion 1, graft portion 2, ..., graft portion n (n is an integer of 2 or more). The graft portion is composed of graft portion 1, graft portion 2, ..., and graft portion n The graft portion may include a composite of graft portion 1, graft portion 2, ..., and graft portion n The polymer may contain one polymer obtained by multi-stage polymerization of a plurality of types of graft portions. A polymer obtained by multi-stage polymerization of a plurality of types of graft portions is also called a multi-stage polymerization graft portion. The method for producing the multi-stage polymerization graft portion will be described in detail later.
[0099] When the graft portion is composed of multiple types of graft portions, not all of these multiple types of graft portions need to be graft-bonded to the elastomer. At least a portion of at least one type of graft portion needs to be graft-bonded to the elastomer, and the other types (multiple other types) of graft portions may be graft-bonded to the graft portion grafted to the elastomer. When the graft portion is composed of multiple types of graft portions, it may have multiple types of polymers (multiple types of non-graft polymers) that have the same structure as the multiple types of graft portions and are not graft-bonded to the elastomer.
[0100] Graft portion 1, graft portion 2, ..., and graft portion n In the multi-stage polymerization graft portion, n The graft part n-1 or a graft portion. n-1 In the multi-stage polymerization graft portion, n Part of the graft n-1 Sometimes it penetrates inside the
[0101] In the multi-stage polymerization graft portion, each of the multiple graft portions may form a layer structure. For example, when the multi-stage polymerization graft portion is composed of graft portions 1, 2, and 3, an embodiment in which graft portion 1 forms the innermost layer in the graft portion, a layer of graft portion 2 is formed on the outer side of graft portion 1, and a layer of graft portion 3 is formed as the outermost layer on the outer side of the layer of graft portion 2 is also one aspect of the present invention. In this way, a multi-stage polymerization graft portion in which each of the multiple graft portions forms a layer structure can also be called a multi-layer graft portion. That is, in one embodiment of the present invention, the graft portion may include (a) a mixture of multiple types of graft portions, (b) a multi-stage polymerization graft portion, and / or (c) a multi-layer graft portion.
[0102] When the elastomer and the graft portion are polymerized in this order in the production of the polymer microparticles (B), at least a portion of the graft portion can cover at least a portion of the elastomer in the resulting polymer microparticles (B). Polymerization of the elastomer and the graft portion in this order can be said to be multistage polymerization of the elastomer and the graft portion. The polymer microparticles (B) obtained by multistage polymerization of the elastomer and the graft portion can be said to be a multistage polymer.
[0103] When the polymer fine particles (B) are multi-stage polymers, the graft moiety may cover at least a part of the elastomer, or may cover the entire elastomer. When the polymer fine particles (B) are multi-stage polymers, a part of the graft moiety may penetrate into the inside of the elastomer.
[0104] When the polymer microparticles (B) are multistage polymers, the elastomer and the graft portion may form a layer structure. For example, an embodiment in which the elastomer forms the innermost layer (also referred to as a core layer) and the layer of the graft portion is formed as the outermost layer (also referred to as a shell layer) on the outside of the elastomer is also one aspect of the present invention. A structure in which the elastomer is the core layer and the graft portion is the shell layer can be called a core-shell structure. Thus, the polymer microparticles (B) in which the elastomer and the graft portion form a layer structure (core-shell structure) can be called a multilayer polymer or a core-shell polymer. That is, in one embodiment of the present invention, the polymer microparticles (B) may be a multistage polymer and / or a multilayer polymer or a core-shell polymer. However, as long as the graft portion is graft-bonded to the elastomer, the polymer microparticles (B) are not limited to the above structure.
[0105] At least a portion of the graft portion preferably covers at least a portion of the elastomer, in other words, at least a portion of the graft portion preferably exists on the outermost side of the polymer fine particles (B).
[0106] (2-2-3.Surface crosslinked polymer) The rubber-containing graft copolymer preferably has a surface cross-linked polymer in addition to the elastomer and the graft portion grafted to the elastomer. In other words, the polymer fine particles (B) preferably have a surface cross-linked polymer in addition to the elastomer and the graft portion grafted to the elastomer. Hereinafter, an embodiment of the present invention will be described taking as an example a case where the polymer fine particles (B) (e.g., rubber-containing graft copolymer) further have a surface cross-linked polymer. In this case, (a) in the production of the polymer fine particles (B), the blocking resistance can be improved, and (b) in the adhesive, the dispersibility of the polymer fine particles (B) in the epoxy resin (A) is improved. The reasons for this are not particularly limited, but can be assumed as follows: the surface cross-linked polymer covers at least a part of the elastomer, thereby reducing the exposure of the elastomer part of the polymer fine particles (B), and as a result, the elastomers are less likely to stick to each other, thereby improving the dispersibility of the polymer fine particles (B).
[0107] When the polymer microparticles (B) further contain a surface-crosslinked polymer, they can also have the following effects: (a) reducing the viscosity of the resulting adhesive, (b) increasing the crosslink density in the elastomer, and (c) increasing the graft efficiency of the grafted portion. The crosslink density in the elastomer means the degree of the number of crosslinked structures in the entire elastomer.
[0108] The surface cross-linked polymer is composed of a polymer containing, as structural units, 30 to 100% by weight of structural units derived from polyfunctional monomers and 0 to 70% by weight of structural units derived from other vinyl monomers, totaling 100% by weight.
[0109] The polyfunctional monomer that can be used for the polymerization of the surface cross-linked polymer includes the same monomer as the polyfunctional monomer described above. Among these polyfunctional monomers, the polyfunctional monomer that can be preferably used for the polymerization of the surface cross-linked polymer includes allyl methacrylate, ethylene glycol di(meth)acrylate, butylene glycol di(meth)acrylate (e.g., 1,3-butylene glycol dimethacrylate, etc.), butanediol di(meth)acrylate, hexanediol di(meth)acrylate, cyclohexanedimethanol di(meth)acrylate, and polyethylene glycol di(meth)acrylates. These polyfunctional monomers may be used alone or in combination of two or more.
[0110] The polymer fine particles (B) may contain a surface cross-linked polymer polymerized independently of the polymerization of the rubber-containing graft copolymer, or may contain a surface cross-linked polymer polymerized together with the rubber-containing graft copolymer. The polymer fine particles (B) may be a multi-stage polymer obtained by multi-stage polymerization of an elastomer, a surface cross-linked polymer, and a graft portion in this order. In either of these embodiments, the surface cross-linked polymer can cover at least a part of the elastomer.
[0111] The surface cross-linked polymer can be regarded as a part of the elastomer. In other words, the surface cross-linked polymer can be regarded as a part of the rubber-containing graft copolymer, and can also be called a surface cross-linked polymerization part. When the polymer fine particles (B) contain a surface cross-linked polymer, the graft part may be (a) grafted to an elastomer other than the surface cross-linked polymer, (b) grafted to a surface cross-linked polymer, or (c) grafted to both an elastomer other than the surface cross-linked polymer and a surface cross-linked polymer. When the polymer fine particles (B) contain a surface cross-linked polymer, the volume average particle diameter of the elastomer mentioned above refers to the volume average particle diameter of the elastomer containing the surface cross-linked polymer.
[0112] The case where the polymer microparticle (B) is a multi-stage polymer obtained by multi-stage polymerization of an elastomer, a surface cross-linked polymer, and a graft portion in this order (case D) will be described. In case D, the surface cross-linked polymer may cover a part of the elastomer, or may cover the whole of the elastomer. In case D, a part of the surface cross-linked polymer may penetrate into the inside of the elastomer. In case D, the graft portion may cover a part of the surface cross-linked polymer, or may cover the whole of the surface cross-linked polymer. In case D, a part of the graft portion may penetrate into the inside of the surface cross-linked polymer. In case D, the elastomer, the surface cross-linked polymer, and the graft portion may have a layer structure. For example, an embodiment in which the elastomer is the innermost layer (core layer), a layer of the surface cross-linked polymer exists outside the elastomer as an intermediate layer, and a layer of the graft portion exists outside the surface cross-linked polymer as an outermost layer (shell layer) is also one embodiment of the present invention.
[0113] (2-2-4. Physical properties of polymer particles (B)) The physical properties of the polymer fine particles (B) will be described below.
[0114] (Volume average particle size (Mv) of polymer microparticles (B)) The volume average particle diameter (Mv) of the polymer fine particles (B) is preferably 0.03 μm to 50.00 μm, more preferably 0.05 μm to 10.00 μm, more preferably 0.08 μm to 2.00 μm, even more preferably 0.10 μm to 1.00 μm, even more preferably 0.10 μm to 0.80 μm, and particularly preferably 0.10 μm to 0.50 μm, because an adhesive having a desired viscosity and high stability can be obtained. When the volume average particle diameter (Mv) of the polymer fine particles (B) is within the above range, there is also an advantage that the dispersibility of the polymer fine particles (B) in the epoxy resin (A) is improved. In this specification, the "volume average particle diameter (Mv) of the polymer fine particles (B)" refers to the volume average particle diameter of the primary particles of the polymer fine particles (B), unless otherwise specified. The volume average particle diameter of the polymer microparticles (B) can be measured using a dynamic light scattering particle size distribution measuring device or the like, using an aqueous latex containing the polymer microparticles (B) as a sample. The volume average particle diameter of the polymer microparticles (B) can be measured using the obtained imaging data (image) by cutting the adhesive layer and imaging the cut surface using an electron microscope or the like.
[0115] The number distribution of the volume average particle diameter of the polymer microparticles (B) in the epoxy resin (A) preferably has a half-value width of 0.5 to 1 times the volume average particle diameter, since this results in an adhesive that is low in viscosity and easy to handle.
[0116] (Glass transition temperature of polymer fine particles (B)) The glass transition temperature of the polymer microparticles (B) is preferably 80°C or less, more preferably 70°C or less, more preferably 60°C or less, more preferably 50°C or less, more preferably 40°C or less, more preferably 30°C or less, more preferably 20°C or less, more preferably 10°C or less, more preferably 0°C or less, more preferably -20°C or less, more preferably -40°C or less, more preferably -45°C or less, more preferably -50°C or less, more preferably -55°C or less, more preferably -60°C or less, more preferably -65°C or less, more preferably -70°C or less, more preferably -75°C or less, more preferably -80°C or less, more preferably -85°C or less, more preferably -90°C or less, more preferably -95°C or less, more preferably -100°C or less, more preferably -105°C or less, more preferably -110°C or less, more preferably -115°C or less, even more preferably -120°C or less, and particularly preferably -125°C or less. According to this configuration, an adhesive having a low glass transition temperature (Tg) can be obtained. As a result, the adhesive can provide an adhesive layer having excellent toughness. Also, the viscosity of the adhesive can be made lower.
[0117] The glass transition temperature (Tg) of the polymer microparticles (B) can be determined by the composition of the structural units contained in each of the elastomers and / or graft moieties contained in the polymer microparticles (B) etc. In other words, the glass transition temperature (Tg) of the resulting polymer microparticles (B) can be adjusted by changing the composition of the monomers used when producing (polymerizing) the polymer microparticles (B).
[0118] The glass transition temperature (Tg) of the polymer microparticles (B) can be measured by a known method. For example, a flat plate made of the polymer microparticles (B) is used to perform dynamic viscoelasticity measurement under tensile conditions using a dynamic viscoelasticity measuring device DVA-200 (IT Measurement and Control Co., Ltd.) to obtain a tan δ graph. The peak temperature of tan δ in the obtained tan δ graph is taken as the glass transition temperature. When two peaks are obtained in the tan δ graph, the lower peak temperature is taken as the glass transition temperature of the polymer microparticles (B). In other words, the glass transition temperature of the polymer microparticles (B) can also be said to be the glass transition temperature of the above-mentioned elastic body.
[0119] (2-2-5. Method for producing polymer microparticles (B)) The polymer fine particles (B) can be produced by polymerizing an elastomer, and then graft polymerizing a polymer that constitutes a graft moiety onto the elastomer in the presence of the elastomer.
[0120] The polymer microparticles (B) can be produced by known methods, such as emulsion polymerization, suspension polymerization, and microsuspension polymerization. Specifically, the polymerization of the elastomer in the polymer microparticles (B), the polymerization of the graft portion (graft polymerization), and the polymerization of the surface cross-linked polymer can be carried out by known methods, such as emulsion polymerization, suspension polymerization, and microsuspension polymerization. Among these, the emulsion polymerization method is particularly preferred as a method for producing the polymer microparticles (B). The emulsion polymerization method has the advantages of (a) easy composition design of the polymer microparticles (B), (b) easy industrial production of the polymer microparticles (B), and (c) easy production of an aqueous latex of the polymer microparticles (B) that can be suitably used in the production of adhesives. Hereinafter, the method for producing the elastomer, graft portion, and surface cross-linked polymer of any configuration that can be contained in the polymer microparticles (B) will be described.
[0121] (Method of manufacturing elastic body) Consider the case where the elastomer contains at least one selected from the group consisting of diene rubber and (meth)acrylate rubber. In this case, the elastomer can be produced by a method such as emulsion polymerization, suspension polymerization, or microsuspension polymerization, and the production method thereof can be, for example, the method described in WO2005 / 028546.
[0122] Consider the case where the elastomer contains an organosiloxane rubber. In this case, the elastomer can be produced by a method such as emulsion polymerization, suspension polymerization, or microsuspension polymerization, and the production method can be, for example, the method described in WO2006 / 070664.
[0123] The "elastic body" of the polymer microparticle (B) is a plurality of types of elastomers (e.g., elastomer 1, elastomer 2, ..., elastomer n In this case, the elastic body 1, the elastic body 2, ..., the elastic body n Alternatively, the elastomers may be polymerized separately by the above-mentioned method, and then mixed and composited to produce a composite of multiple elastomers. n may be sequentially polymerized in multiple stages to produce one elastomer composed of multiple types of elastomers.
[0124] The multi-stage polymerization of elastomers will now be described in detail. For example, a multi-stage polymerized elastomer can be obtained by carrying out the steps (1) to (4) below in order: (1) polymerizing elastomer 1 to obtain elastomer 1; (2) subsequently polymerizing elastomer 2 in the presence of elastomer 1 to obtain a two-stage elastomer. 1+2 (3) Then, the elastic body is obtained. 1+2 In the presence of 1+2+3 (4) After the same procedure, the elastic body is 1+2+···+(n-1) In the presence of elastic n Multi-stage polymerized elastomer 1+2+···+n get.
[0125] (Method of manufacturing the graft part) The graft portion can be formed, for example, by polymerizing the monomer used for forming the graft portion by known radical polymerization. When (a) the elastomer or (b) the polymer microparticle precursor containing the elastomer and the surface cross-linked polymer is obtained as an aqueous latex, it is preferable to carry out the polymerization of the graft portion by emulsion polymerization. The graft portion can be produced, for example, according to the method described in WO2005 / 028546.
[0126] The graft portion is a portion having a plurality of types of graft portions (e.g., graft portion 1, graft portion 2, ..., graft portion n A method for producing a graft portion in the case where the graft portion is composed of graft portion 1, graft portion 2, ..., graft portion n may be polymerized separately by the above-mentioned method, and then mixed and composited to produce a graft portion (composite) consisting of a plurality of types of graft portions. Alternatively, graft portion 1, graft portion 2, ..., graft portion n may be sequentially polymerized in multiple stages to produce one graft moiety consisting of multiple types of graft moieties.
[0127] The multi-stage polymerization of the graft portion will be specifically described. For example, a multi-stage polymerization graft portion can be obtained by carrying out the following steps (1) to (4) in order: (1) polymerizing graft portion 1 to obtain graft portion 1; (2) subsequently polymerizing graft portion 2 in the presence of graft portion 1 to obtain a two-stage graft portion. 1+2 (3) Then, the graft part is obtained. 1+2 The graft portion 3 is polymerized in the presence of 1+2+3 (4) After the same procedure, the graft part is obtained. 1+2+···+(n-1) In the presence of n The multi-stage polymerization graft part is obtained by polymerizing 1+2+···+n get.
[0128] When the graft moiety is composed of a plurality of types of graft moieties, the graft moieties may be polymerized and then graft polymerized onto the elastomer to produce the polymer fine particles (B). The polymer fine particles (B) may be produced by sequentially graft polymerizing the plurality of types of polymers constituting the graft moieties onto the elastomer in the presence of the elastomer in multiple stages.
[0129] (Method of producing surface cross-linked polymer) The surface cross-linked polymer can be formed by polymerizing the monomer used for forming the surface cross-linked polymer by known radical polymerization. When the elastomer is obtained as an aqueous latex, the polymerization of the surface cross-linked polymer is preferably carried out by emulsion polymerization.
[0130] When emulsion polymerization is employed as the method for producing the polymer fine particles (B), a known emulsifier (dispersant) can be used for producing the polymer fine particles (B).
[0131] Examples of emulsifiers include anionic emulsifiers, nonionic emulsifiers, polyvinyl alcohol, alkyl-substituted cellulose, polyvinylpyrrolidone, polyacrylic acid derivatives, etc. Examples of anionic emulsifiers include sulfur-based emulsifiers, phosphorus-based emulsifiers, sarcosinic acid-based emulsifiers, carboxylic acid-based emulsifiers, etc. Examples of sulfur-based emulsifiers include sodium dodecylbenzenesulfonate (abbreviation: SDBS), etc. Examples of phosphorus-based emulsifiers include sodium polyoxyethylene lauryl ether phosphate, etc.
[0132] When the emulsion polymerization method is used as the method for producing the polymer microparticles (B), a thermally decomposable initiator can be used for producing the polymer microparticles (B). Examples of the thermally decomposable initiator include known initiators such as (a) 2,2'-azobisisobutyronitrile and (b) peroxides such as organic peroxides and inorganic peroxides. Examples of the organic peroxides include t-butylperoxyisopropyl carbonate, paramenthane hydroperoxide, cumene hydroperoxide, dicumyl peroxide, t-butyl hydroperoxide, di-t-butyl peroxide, and t-hexyl peroxide. Examples of the inorganic peroxides include hydrogen peroxide, potassium persulfate, and ammonium persulfate.
[0133] A redox type initiator can also be used to produce the polymer microparticles (A). The redox type initiator is an initiator in which (a) a peroxide such as an organic peroxide or an inorganic peroxide is used in combination with (b) a transition metal salt such as iron sulfate (II), or a reducing agent such as sodium formaldehyde sulfoxylate or glucose. If necessary, a chelating agent such as disodium ethylenediaminetetraacetate and a phosphorus-containing compound such as sodium pyrophosphate may also be used in combination.
[0134] When a redox type initiator is used, polymerization can be performed even at a low temperature where the peroxide does not substantially decompose thermally, and the polymerization temperature can be set in a wide range. Therefore, it is preferable to use a redox type initiator. Among redox type initiators, redox type initiators using organic peroxides such as cumene hydroperoxide, dicumyl peroxide, paramenthane hydroperoxide, and t-butyl hydroperoxide as peroxides are preferable. The amount of the initiator used, and the amount of the reducing agent, transition metal salt, chelating agent, etc. used when a redox type initiator is used can be within a known range.
[0135] When a polyfunctional monomer is used in the polymerization of the elastomer, the graft portion or the surface cross-linked polymer for the purpose of introducing a cross-linked structure into the elastomer, the graft portion or the surface cross-linked polymer, a known chain transfer agent can be used within a known range of use amount. By using the chain transfer agent, the molecular weight and / or the degree of cross-linking of the obtained elastomer, the graft portion or the surface cross-linked polymer can be easily adjusted.
[0136] In addition to the above-mentioned components, a surfactant may be used in the production of the polymer microparticles (B). The type and amount of the surfactant are within the known ranges.
[0137] In the production of the polymer fine particles (B), the polymerization conditions such as polymerization temperature, pressure, and deoxidation may be appropriately set within known numerical ranges.
[0138] (2-3. Non-crosslinked acrylic resin (C)) The non-crosslinked acrylic resin (C) may be any non-crosslinked acrylic polymer. The acrylic polymer is a polymer mainly composed of a structural unit consisting of an acrylic acid ester monomer and / or a methacrylic acid ester monomer. The "structural unit consisting of an acrylic acid ester monomer and / or a methacrylic acid ester monomer" can also be called a "structural unit derived from an acrylic acid ester monomer and / or a methacrylic acid ester monomer."
[0139] The acrylic acid ester monomer preferably has an ester moiety having a carbon number of 1 to 20. The methacrylic acid ester monomer preferably has an ester moiety having a carbon number of 1 to 20. Examples of the acrylic polymer include (a) a homopolymer of an acrylic acid ester monomer, (b) a homopolymer of a methacrylic acid ester monomer, and (c) a copolymer of an acrylic acid ester monomer and / or a methacrylic acid ester monomer with a monomer such as an unsaturated fatty acid, an acrylamide monomer, a maleimide monomer, or vinyl acetate, or a vinyl copolymer (hereinafter also referred to as an acrylic copolymer).
[0140] Examples of the acrylic acid ester monomer or methacrylic acid ester monomer include methyl acrylate (MA), ethyl acrylate (EA), 2-ethylhexyl acrylate (2EHA), acrylic acid (AA), methacrylic acid (MAA), 2-hydroxyethyl acrylate (2HEA), 2-hydroxyethyl methacrylate (2HEMA), butyl acrylate (BA), methyl methacrylate (MMA), ethyl methacrylate (EMA), n-butyl methacrylate (nBMA), isobutyl methacrylate (iBMA), propyl acrylate, isopropyl acrylate, and acrylate (AA). Examples of such acrylates include isobutyl acrylate, t-butyl acrylate, neopentyl acrylate, isodecyl acrylate, lauryl acrylate, tridecyl acrylate, stearyl acrylate, cyclohexyl acrylate, isobornyl acrylate, tricyclodecyl acrylate, hydroxyethyl acrylate, hydroxybutyl acrylate, hydroxypropyl acrylate, hydroxyethyl acrylate, 2-methoxyethyl acrylate, dimethylaminoethyl acrylate, chloroethyl acrylate, trifluoroethyl acrylate, tetrahydrofurfuryl acrylate, etc. These may be used alone or in combination of two or more.
[0141] In the acrylic copolymer, the ratio of (a) a structural unit derived from an acrylic acid ester monomer and / or a methacrylic acid ester monomer (structural unit (a)) to (b) a structural unit derived from a monomer such as an unsaturated fatty acid, an acrylamide monomer, a maleimide monomer, or a vinyl acetate monomer, or a vinyl copolymer (structural unit (b)) is preferably 50% by weight to 100% by weight for the structural unit (a) and 0% by weight to 50% by weight for the structural unit (b).
[0142] The acrylic polymer preferably contains 50% by weight or more of structural units derived from butyl acrylate (BA), more preferably 60% by weight or more, even more preferably 70% by weight or more, particularly preferably 80% by weight or more, and most preferably 90% by weight or more.
[0143] The vinyl copolymer is obtained by copolymerizing a mixture of vinyl monomers containing one or more selected from the group consisting of aromatic vinyl monomers, cyanide vinyl monomers, and unsaturated carboxylic acid alkyl ester monomers. The mixture of vinyl monomers may further contain another monomer (hereinafter also referred to as monomer C) that is copolymerizable with the vinyl monomers constituting the above-mentioned group.
[0144] Examples of the aromatic vinyl monomer include styrene, α-methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, t-butylstyrene, and vinyltoluene. These vinyl monomers may be used alone or in combination of two or more. Among these, styrene is preferred from the viewpoint of easily increasing the refractive index.
[0145] The unsaturated carboxylic acid alkyl ester monomer is not particularly limited. For example, an ester of an alcohol having 1 to 6 carbon atoms with acrylic acid or methacrylic acid is preferable. The ester of an alcohol having 1 to 6 carbon atoms with acrylic acid or methacrylic acid may further have a substituent such as a hydroxyl group or a halogen group.
[0146] Examples of esters of alcohols having 1 to 6 carbon atoms with acrylic acid or methacrylic acid include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, t-butyl (meth)acrylate, n-hexyl (meth)acrylate, cyclohexyl (meth)acrylate, chloromethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2,3,4,5,6-pentahydroxyhexyl (meth)acrylate, 2,3,4,5-tetrahydroxypentyl (meth)acrylate, etc. These may be used alone or in combination of two or more.
[0147] Examples of vinyl cyanide monomers include acrylonitrile, methacrylonitrile, ethacrylonitrile, etc. These may be used alone or in combination of two or more.
[0148] Monomer C is a vinyl monomer other than the aromatic vinyl monomer, the unsaturated carboxylic acid alkyl ester monomer, and the vinyl cyanide monomer, and is not particularly limited as long as it does not impair the effects of the present invention. Specific examples of monomer C include unsaturated fatty acids, acrylamide monomers, maleimide monomers, vinyl acetate, and acrylic acid ester monomers. These may be used alone or in combination of two or more.
[0149] The unsaturated fatty acid may be selected, for example, from itaconic acid, maleic acid, fumaric acid, butenoic acid, acrylic acid, methacrylic acid, and the like.
[0150] The acrylamide monomer may be selected from, for example, acrylamide, methacrylamide, N-methylacrylamide, and the like.
[0151] The maleimide monomer may be selected from, for example, N-methylmaleimide, N-ethylmaleimide, N-isopropylmaleimide, N-butylmaleimide, N-hexylmaleimide, N-octylmaleimide, N-dodecylmaleimide, N-cyclohexylmaleimide, N-phenylmaleimide, and the like.
[0152] The method for producing the vinyl copolymer is not particularly limited, but examples thereof include emulsion polymerization, suspension polymerization, bulk polymerization, and solution polymerization.
[0153] In the method for producing a vinyl copolymer, a polymerization initiator may be used as necessary. The polymerization initiator may be, for example, one or more appropriately selected from the group consisting of peroxides, azo compounds, potassium persulfate, etc. The amount of the polymerization initiator to be added is not particularly limited.
[0154] Examples of peroxides include benzoyl peroxide, cumene hydroperoxide, dicumyl peroxide, diisopropylbenzene hydroperoxide, t-butyl hydroperoxide, t-butyl peroxyacetate, t-butyl peroxybenzoate, t-butyl isopropyl carbonate, di-t-butyl peroxide, t-butyl peroctate, 1,1-bis(t-butylperoxy)3,3,5-trimethylcyclohexane, 1,1-bis(t-butylperoxy)cyclohexane, and t-butylperoxy-2-ethylhexanoate. Among these, cumene hydroperoxide, 1,1-bis(t-butylperoxy)3,3,5-trimethylcyclohexane, and 1,1-bis(t-butylperoxy)cyclohexane are particularly preferably used.
[0155] Examples of the azo compounds include azobisisobutyronitrile, azobis(2,4-dimethylvaleronitrile), 2-phenylazo-2,4-dimethyl-4-methoxyvaleronitrile, 2-cyano-2-propylazoformamide, 1,1'-azobiscyclohexane-1-carbonitrile, azobis(4-methoxy-2,4-dimethylvaleronitrile), dimethyl 2,2'-azobisisobutyrate, 1-t-butylazo-2-cyanobutane, and 2-t-butylazo-2-cyano-4-methoxy-4-methylpentane. Among them, 1,1'-azobiscyclohexane-1-carbonitrile is particularly preferably used.
[0156] Specific examples of vinyl copolymers include polyvinyl chloride, chlorinated polyvinyl chloride, polystyrene, styrene-acrylonitrile copolymer, styrene-acrylonitrile-N-phenylmaleimide copolymer, α-methylstyrene-acrylonitrile copolymer, polymethyl methacrylate, methyl methacrylate-styrene copolymer, etc. These may be used alone or in combination of two or more.
[0157] The adhesive contains 1 to 100 parts by mass of non-crosslinked acrylic resin (C), more preferably 1 to 50 parts by mass of non-crosslinked acrylic resin (C), more preferably 1 to 30 parts by mass of non-crosslinked acrylic resin (C), more preferably 1 to 20 parts by mass of non-crosslinked acrylic resin (C), more preferably 1 to 10 parts by mass of non-crosslinked acrylic resin (C), and most preferably 1 to 5 parts by mass of non-crosslinked acrylic resin (C) relative to 100 parts by mass of epoxy resin (A). The more non-crosslinked acrylic resin (C) is contained, the better the peeling mode of the adhesive can be.
[0158] When the total of the polymer fine particles (B) and the non-crosslinked acrylic resin (C) is taken as 100% by weight, (i) preferably, the polymer fine particles (B) are 50-99% by weight, and the non-crosslinked acrylic resin (C) is 1-50% by weight, (ii) more preferably, the polymer fine particles (B) are 70-99% by weight, and the non-crosslinked acrylic resin (C) is 1-30% by weight, (iii) more preferably, the polymer fine particles (B) are 80-99% by weight, and the non-crosslinked acrylic resin (C) is 1-20% by weight, (iv) more preferably, the polymer fine particles (B) are 90-99% by weight, and the non-crosslinked acrylic resin (C) is 1-10% by weight, and (v) most preferably, the polymer fine particles (B) are 95-99% by weight, and the non-crosslinked acrylic resin (C) is 1-5% by weight. According to the above-mentioned constitution, the peeling mode can be improved.
[0159] Since the dispersibility of the polymer fine particles (B) in the epoxy resin (A) is good, when the total of the polymer fine particles (B) and the non-crosslinked acrylic resin (C) is taken as 100% by weight, (i) preferably, the polymer fine particles (B) are 50 to 95% by weight and the non-crosslinked acrylic resin (C) is 5 to 50% by weight, (ii) more preferably, the polymer fine particles (B) are 50 to 90% by weight and the non-crosslinked acrylic resin (C) is 10 to 50% by weight, (iii) more preferably, the polymer fine particles (B) are 50 to 85% by weight and the non-crosslinked acrylic resin (C) is 15 to 50% by weight, (iv) more preferably, the polymer fine particles (B) are 50 to 80% by weight and the non-crosslinked acrylic resin (C) is 20 to 50% by weight, and (v) most preferably, the polymer fine particles (B) are 60 to 80% by weight and the non-crosslinked acrylic resin (C) is 20 to 40% by weight.
[0160] The weight average molecular weight of the non-crosslinked acrylic resin (C) is not particularly limited, but is preferably not more than 100,000, more preferably not more than 80,000, more preferably not more than 50,000, more preferably not more than 30,000, more preferably not more than 20,000, and most preferably not more than 10,000. According to the above-mentioned configuration, an increase in the viscosity of the adhesive can be suppressed, and the viscosity of the adhesive can be made more favorable.
[0161] The glass transition temperature of the non-crosslinked acrylic resin (C) is not particularly limited, but is preferably not more than 80° C., more preferably not more than 70° C., more preferably not more than 60° C., more preferably not more than 50° C., more preferably not more than 40° C., more preferably not more than 30° C., more preferably not more than 20° C., more preferably not more than 10° C., more preferably not more than 0° C., more preferably not more than −10° C., more preferably not more than −20° C., more preferably not more than −30° C., more preferably not more than −40° C., and more preferably not more than −50° C. According to the above configuration, a decrease in the peel strength of the adhesive can be suppressed.
[0162] The viscosity of the non-crosslinked acrylic resin (C) is not particularly limited, but is preferably 1,000,000 mPa·s or less at 25°C, more preferably 500,000 mPa·s or less at 25°C, more preferably 200,000 mPa·s or less at 25°C, more preferably 100,000 mPa·s or less at 25°C, and most preferably 50,000 mPa·s or less at 25°C. In other words, the non-crosslinked acrylic resin (C) is preferably in a liquid state. With this configuration, an increase in the viscosity of the adhesive can be suppressed.
[0163] It is preferable that the non-crosslinked acrylic resin (C) forms a domain in the cured product when the adhesive is cured to obtain a cured product. The average particle size of the polymer fine particles (B) is preferably larger than the major axis of the domain. The average particle size of the polymer fine particles (B) and the major axis of the domain can each be measured by scanning electron microscopy (SEM method). The average particle size of the polymer fine particles (B) means the average diameter of a circle (diameter equivalent to an area circle) equal to the projected area of 30 randomly selected polymer fine particles (B) in an SEM image. The major axis of the domain means the average of the maximum length (the length of the longest straight line among the straight lines connecting two points on the periphery) of 30 randomly selected non-crosslinked acrylic resin (C) fine particles in an SEM image. For example, FIG. 1 is an SEM image of the cured product of the adhesive of Example 3 obtained by the method described below. In the SEM image, "10" indicates the polymer fine particles (B) and "20" indicates the domain of the non-crosslinked acrylic resin (C).
[0164] The major axis length of the domain of the non-crosslinked acrylic resin (C) is preferably 1 nm or more and 500 μm or less, more preferably 10 nm or more and 100 μm or less, still more preferably 10 nm or more and 10 μm or less, and most preferably 10 nm or more and 1 μm or less. For example, the major axis lengths of a predetermined number (for example, 10, 100, or 1000) of domains can be measured with a microscope, and the major axis length of the domain can be calculated as the average value of the measured lengths. Further, the major axis length of the domain can also be calculated according to the method described in the examples below. According to the above configuration, the peeling mode can be made better.
[0165] The proportion (lower limit value) of the presence of the domain in the cured product of the adhesive is not particularly limited, but is preferably 1% or more, more preferably 2% or more, and most preferably 3% or more. The proportion (upper limit value) of the presence of the domain in the cured product of the adhesive is not particularly limited, but is preferably 50% or less, more preferably 40% or less, still more preferably 30% or less, still more preferably 20% or less, and most preferably 10% or less. For example, by observing the surface or cross section of the cured product with a microscope, measuring the area (A) occupied by the domain and the area (B) occupied by other than the domain on the surface or cross section, the proportion of the presence of the domain can be calculated as "A÷(A + B)×100" (%). Further, the proportion can also be calculated according to the method described in the examples below. According to the above configuration, the peeling mode can be made better.
[0166] The major axis length of the domain is preferably smaller than the average particle diameter of the polymer fine particles (B). For example, when the value of the major axis length of the domain is "a" and the value of the average particle diameter of the polymer fine particles (B) is "b", it is preferable that "a < b", "10×a < b", "100×a < b", or "1000×a < b". According to the above configuration, the peeling mode can be made better.
[0167] (1 - 4. Optional components) The adhesive according to one embodiment of the present invention may contain optional components other than the above-mentioned components. The optional components include a curing agent, a curing accelerator, a reinforcing agent, a colorant (e.g., a pigment and a dye), a body pigment, a pigment dispersant, an ultraviolet absorber, an antioxidant, a heat stabilizer (gelling inhibitor), a plasticizer, a leveling agent, an antifoaming agent, a silane coupling agent, an antistatic agent, a flame retardant, a lubricant, a viscosity reducing agent, a viscosity adjusting agent, a thixotropic agent, a shrinkage reducing agent, an inorganic filler, an organic filler, a thermoplastic resin, a drying agent, a dispersing agent, a thermal conductivity improving agent, a water binding agent, an anti-sagging agent, a color separation preventing agent, a settling preventing agent, an adhesive layer wear adjusting agent, a surface adjusting agent, a monobasic organic acid, camphor, castor oil, etc.
[0168] More specifically, the optional components include an epoxy curing agent; a curing accelerator; and a reinforcing agent such as a rubber-modified epoxy resin, a urethane-modified epoxy resin, or a blocked urethane. If the adhesive contains an epoxy curing agent, the adhesive can be easily cured. If the adhesive contains a curing accelerator, the adhesive can be easily cured. If the adhesive contains a reinforcing agent, the adhesive can be further improved in performance such as toughness, impact resistance, shear adhesion, and peel adhesion of the cured product (adhesive layer).
[0169] Specific examples of epoxy curing agents include components that become active upon heating (sometimes referred to as latent epoxy curing agents). Examples of such latent epoxy curing agents include nitrogen (N)-containing curing agents, such as specific amine-based curing agents (including imine-based curing agents). Examples of epoxy curing agents include boron trichloride / amine complexes, boron trifluoride / amine complexes, dicyandiamide, melamine, diallylmelamine, guanamines (e.g., acetoguanamine and benzoguanamine), aminotriazoles (e.g., 3-amino-1,2,4-triazole), hydrazides (e.g., adipic acid dihydrazide, stearic acid dihydrazide, isophthalic acid dihydrazide, semicarbazide), cyanoacetamide, and aromatic polyamines (e.g., metaphenylenediamine, diaminodiphenylmethane, diaminodiphenylsulfone, etc.). As the epoxy curing agent, it is more preferable to use dicyandiamide, isophthalic acid dihydrazide, adipic acid dihydrazide, and / or 4,4'-diaminodiphenyl sulfone, and it is particularly preferable to use dicyandiamide, because these have excellent adhesive properties.
[0170] Among the epoxy hardeners, latent epoxy hardeners are preferred because they enable the adhesive to be used as a one-component adhesive.
[0171] Next, we will explain the case where the adhesive is used as a two-component or multi-component adhesive. In this case, amine-based curing agents (including imine-based curing agents) and / or mercaptan-based curing agents other than those mentioned above can be selected as epoxy curing agents that are active at relatively low temperatures around room temperature (sometimes called room temperature curing curing agents).
[0172] Examples of such epoxy curing agents that are active at relatively low temperatures around room temperature include (a) amine-based curing agents such as polyamidoamines, amine-terminated polyethers, amine-terminated rubbers, modified aliphatic polyamines, modified alicyclic polyamines, and polyamides, and (b) various compounds described in paragraph
[0113] of the specification of WO2016-163491.
[0173] Amine-terminated polyethers, which contain a polyether backbone and an average of 1 to 4 (preferably 1.5 to 3) amino and / or imino groups per molecule, can also be used as epoxy curing agents that are active at relatively low temperatures, such as room temperature. Commercially available amine-terminated polyethers include Jeffamine D-230, Jeffamine D-400, Jeffamine D-2000, Jeffamine D-4000, and Jeffamine T-5000, all manufactured by Huntsman.
[0174] Furthermore, amine-terminated rubbers containing a conjugated diene polymer main chain and having an average of 1 to 4 (more preferably 1.5 to 3) amino and / or imino groups per molecule can also be used as epoxy curing agents that are active at relatively low temperatures around room temperature. Here, the main chain of the rubber, i.e., the conjugated diene polymer main chain, is preferably a polybutadiene homopolymer or copolymer, more preferably a polybutadiene / acrylonitrile copolymer, and particularly preferably a polybutadiene / acrylonitrile copolymer in which the acrylonitrile monomer content in 100% by mass of the polymer main chain is 5 to 40% by mass (more preferably 10 to 35% by mass, even more preferably 15 to 30% by mass). Examples of commercially available amine-terminated rubbers include Hypro 1300X16 ATBN manufactured by CVC Corporation.
[0175] Among the above amine-based curing agents that are active at relatively low temperatures around room temperature, polyamidoamines, amine-terminated polyethers, and amine-terminated rubbers are more preferred, and it is particularly preferred to use polyamidoamines, amine-terminated polyethers, and amine-terminated rubbers in combination.
[0176] In addition, among epoxy curing agents, acid anhydrides and phenols can also be used as latent epoxy curing agents. Acid anhydrides and phenols require higher temperatures than amine curing agents, but have a longer pot life, and the resulting adhesive layer has a good balance of physical properties such as electrical properties, chemical properties, and mechanical properties. Examples of acid anhydrides include various compounds described in paragraph
[0117] of the specification of WO2016-163491.
[0177] The epoxy curing agent may be used alone or in combination of two or more kinds.
[0178] The amount of the epoxy curing agent contained in the adhesive is not limited, but is preferably 1 to 80 parts by mass, more preferably 1 to 50 parts by mass, and most preferably 1 to 30 parts by mass, relative to 100 parts by mass of the epoxy resin (A). According to the above-mentioned configuration, the above-mentioned advantages of including the epoxy curing agent can be further improved.
[0179] Specific examples of the curing accelerator include (a) ureas such as p-chlorophenyl-N,N-dimethylurea (trade name: Monuron), 3-phenyl-1,1-dimethylurea (trade name: Fenuron), 3,4-dichlorophenyl-N,N-dimethylurea (trade name: Diuron), N-(3-chloro-4-methylphenyl)-N',N'-dimethylurea (trade name: Chlortoluron), and 1,1-dimethylphenylurea (trade name: Dyhard); (b) benzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, 2-(dimethylaminomethyl)phenol, and the like. (c) tertiary amines such as C1-C12 alkylene imidazole, N-arylimidazole, 2-methylimidazole, 2-ethyl-2-methylimidazole, N-butylimidazole, 1-cyanoethyl-2-undecylimidazolium trimellitate, and addition products of epoxy resins and imidazole; and (d) 6-caprolactam. Tertiary amines and imidazoles can be used in combination with an amine-based epoxy curing agent (e.g., a room temperature curing agent) other than dicyandiamide to improve the curing speed and the physical properties and heat resistance of the resulting adhesive layer. The curing accelerator may be used alone or in combination of two or more types.
[0180] The amount of the epoxy curing accelerator contained in the adhesive is not limited, but is preferably 0.1 to 10 parts by mass, more preferably 0.1 to 8 parts by mass, and most preferably 0.1 to 5 parts by mass, relative to 100 parts by mass of the epoxy resin (A). According to the above-mentioned configuration, the above-mentioned advantages of including the curing accelerator can be further improved.
[0181] The curing accelerators may be used alone or in combination of two or more kinds.
[0182] <Rubber-modified epoxy resin> The rubber-modified epoxy resin is a reaction product obtained by reacting rubber with an epoxy group-containing compound, and has an average of 1.1 or more epoxy groups per molecule, preferably 2 or more. Examples of the rubber include rubber-based polymers such as acrylonitrile butadiene rubber (NBR); styrene butadiene rubber (SBR); hydrogenated nitrile rubber (HNBR); ethylene propylene rubber (EPDM); acrylic rubber (ACM); butyl rubber (IIR); butadiene rubber; and polyoxyalkylenes such as polypropylene oxide, polyethylene oxide, and polytetramethylene oxide. The rubber-based polymer is preferably one having a reactive group such as an amino group, a hydroxyl group, or a carboxyl group at its terminal. The rubber-modified epoxy resin is preferably a product obtained by reacting these rubber-based polymers with an epoxy resin at an appropriate compounding ratio by a known method. Among these, the rubber-modified epoxy resin is preferably an acrylonitrile-butadiene rubber-modified epoxy resin or a polyoxyalkylene-modified epoxy resin from the viewpoint of the adhesiveness and impact peel adhesion of the adhesive obtained, and more preferably an acrylonitrile-butadiene rubber-modified epoxy resin. The acrylonitrile-butadiene rubber-modified epoxy resin is obtained, for example, by reacting a carboxyl-terminated NBR (CTBN) with a bisphenol A type epoxy resin.
[0183] The content of the acrylonitrile monomer component in 100 mass% of the acrylonitrile-butadiene rubber (NBR) is preferably 5 to 40 mass%, more preferably 10 to 35 mass%, and even more preferably 15 to 30 mass%, from the viewpoint of (a) the adhesion and impact peel adhesion of the resulting adhesive, and (b) the content of the acrylonitrile monomer component in 100 mass% of the acrylonitrile-butadiene rubber (NBR) is preferably 5 to 40 mass%, more preferably 10 to 35 mass%, and even more preferably 15 to 30 mass%, from the viewpoint of the workability of the resulting adhesive, and particularly preferably 20 to 30 mass%.
[0184] In addition, for example, an addition reaction product (hereinafter also referred to as "adduct") between an amino-terminated polyoxyalkylene and an epoxy resin is also included in the rubber-modified epoxy resin. The adduct can be easily produced by a known method, for example, as described in U.S. Pat. No. 5,084,532 and U.S. Pat. No. 6,015,865. The epoxy resin used in producing the adduct can be, for example, the specific example of the epoxy resin (A) exemplified in one embodiment of the present invention, but bisphenol A type epoxy resin and bisphenol F type epoxy resin are preferred, and bisphenol A type epoxy resin is more preferred. The commercially available amino-terminated polyoxyalkylene used in producing the adduct can be, for example, Jeffamine D-230, Jeffamine D-400, Jeffamine D-2000, Jeffamine D-4000, Jeffamine T-5000, etc., manufactured by Huntsman.
[0185] The average number of epoxide reactive end groups per molecule in the rubber is preferably 1.5 to 2.5, and more preferably 1.8 to 2.2. The number average molecular weight of the rubber is preferably 1,000 to 10,000, more preferably 2,000 to 8,000, and particularly preferably 3,000 to 6,000, in terms of polystyrene-equivalent molecular weight measured by GPC.
[0186] There is no particular limitation on the method of producing the rubber-modified epoxy resin, and for example, the rubber and the epoxy group-containing compound can be reacted in a large amount of the epoxy group-containing compound to produce the rubber-modified epoxy resin. Specifically, it is preferable to produce the rubber-modified epoxy resin by reacting 2 equivalents or more of the epoxy group-containing compound per equivalent of the epoxy reactive terminal group in the rubber. It is more preferable to react a sufficient amount of the epoxy group-containing compound so that the resulting product is a mixture of (a) an adduct of the rubber and the epoxy group-containing compound and (b) a free epoxy group-containing compound. For example, the rubber-modified epoxy resin is produced by heating the rubber and the epoxy group-containing compound to a temperature of 100 to 250°C in the presence of a catalyst such as phenyldimethylurea and triphenylphosphine. There is no particular limitation on the epoxy group-containing compound used when producing the rubber-modified epoxy resin, but bisphenol A type epoxy resin and bisphenol F type epoxy resin are preferred, and bisphenol A type epoxy resin is more preferred. In one embodiment of the present invention, when an excessive amount of the epoxy group-containing compound is used in producing the rubber-modified epoxy resin, the unreacted epoxy group-containing compound remaining after the reaction is not included in the rubber-modified epoxy resin of one embodiment of the present invention.
[0187] In the case of rubber-modified epoxy resin, the epoxy resin can be modified by preliminarily reacting an epoxy group-containing compound (epoxy resin) with a bisphenol component. The amount of the bisphenol component used for modification is preferably 3 to 35 parts by mass, more preferably 5 to 25 parts by mass, per 100 parts by mass of the rubber component in the rubber-modified epoxy resin. A cured product obtained by curing an adhesive containing the modified rubber-modified epoxy resin has excellent adhesion durability after exposure to high temperatures, and also has excellent impact resistance at low temperatures.
[0188] The glass transition temperature (Tg) of the rubber-modified epoxy resin is not particularly limited, but is preferably −25° C. or lower, more preferably −35° C. or lower, even more preferably −40° C. or lower, and particularly preferably −50° C. or lower.
[0189] The number average molecular weight of the rubber-modified epoxy resin, in terms of polystyrene as measured by GPC, is preferably 1500 to 40000, more preferably 3000 to 30000, and particularly preferably 4000 to 20000. The molecular weight distribution of the rubber-modified epoxy resin (ratio of weight average molecular weight to number average molecular weight (weight average molecular weight / number average molecular weight)) is preferably 1 to 4, more preferably 1.2 to 3, and particularly preferably 1.5 to 2.5.
[0190] The content of the rubber-modified epoxy resin in the adhesive is preferably 1 to 50 parts by mass, more preferably 2 to 40 parts by mass, further preferably 5 to 30 parts by mass, and particularly preferably 10 to 20 parts by mass, per 100 parts by mass of the epoxy resin (A). When the content of the rubber-modified epoxy resin in the adhesive is (a) 1 part by mass or more per 100 parts by mass of the epoxy resin (A), the obtained cured product tends to be not brittle and to have good impact peel adhesion, and when (b) is 50 parts by mass or less, the obtained cured product tends to have good heat resistance and / or elastic modulus (rigidity).
[0191] The rubber-modified epoxy resins can be used alone or in combination of two or more.
[0192] <Urethane modified epoxy resin> The urethane-modified epoxy resin is a reaction product having an average of 1.1 or more, preferably 2 or more, epoxy groups per molecule, obtained by reacting (a) a compound containing an epoxy group and a group reactive with an isocyanate group with (b) a urethane prepolymer containing an isocyanate group. For example, a urethane-modified epoxy resin can be obtained by reacting a hydroxyl-containing epoxy compound with a urethane prepolymer.
[0193] The number average molecular weight of the urethane-modified epoxy resin, in terms of polystyrene, measured by GPC, is preferably 1500 to 40000, more preferably 3000 to 30000, and particularly preferably 4000 to 20000. The molecular weight distribution (ratio of weight average molecular weight to number average molecular weight (weight average molecular weight / number average molecular weight)) of the urethane-modified epoxy resin is preferably 1 to 4, more preferably 1.2 to 3, and particularly preferably 1.5 to 2.5.
[0194] The content of the urethane-modified epoxy resin in the adhesive is preferably 1 to 50 parts by mass, more preferably 2 to 40 parts by mass, further preferably 5 to 30 parts by mass, and particularly preferably 10 to 20 parts by mass, per 100 parts by mass of the epoxy resin (A). When the content of the urethane-modified epoxy resin in the adhesive is (a) 1 part by mass or more per 100 parts by mass of the epoxy resin (A), the obtained cured product tends to be not brittle and to have good impact peel adhesion, and when (b) is 50 parts by mass or less, the obtained cured product tends to have good heat resistance and / or elastic modulus (rigidity).
[0195] The urethane-modified epoxy resins can be used alone or in combination of two or more.
[0196] <Blocked urethane> Blocked urethane is an elastomer type compound containing urethane groups and / or urea groups and having terminal isocyanate groups, in which all or part of the terminal isocyanate groups are capped with various blocking agents having active hydrogen groups. In particular, compounds in which all of the terminal isocyanate groups are capped with blocking agents are preferred. Such compounds can be obtained, for example, by capping all or part of the isocyanate groups with blocking agents having active hydrogen groups after or simultaneously with the preparation of (i) a polymer (urethane prepolymer) having urethane groups and / or urea groups in the main chain and isocyanate groups at the terminals. The urethane prepolymer can be prepared by reacting an organic polymer having an active hydrogen-containing group at the terminal with an excess of a polyisocyanate compound.
[0197] The blocked urethane is, for example, represented by the following general formula (1): A-(NR 2 -C(=O)-X)a (1) (In the general formula (1), a R 2 are each independently a hydrocarbon group having 1 to 20 carbon atoms. a represents the average number of capped isocyanate groups per molecule, and is preferably 1.1 or more, more preferably 1.5 to 8, even more preferably 1.7 to 6, and particularly preferably 2 to 4. X is a residue obtained by removing an active hydrogen atom from the blocking agent. A is a residue obtained by removing a terminal isocyanate group from an isocyanate-terminated prepolymer.
[0198] The number average molecular weight of the blocked urethane, in terms of polystyrene equivalent molecular weight measured by GPC, is preferably 2000 to 40000, more preferably 3000 to 30000, and particularly preferably 4000 to 20000. The molecular weight distribution of the blocked urethane (ratio of weight average molecular weight to number average molecular weight (weight average molecular weight / number average molecular weight)) is preferably 1 to 4, more preferably 1.2 to 3, and particularly preferably 1.5 to 2.5. The content of the blocked urethane in the adhesive is preferably 1 to 50 parts by mass, more preferably 2 to 40 parts by mass, further preferably 5 to 30 parts by mass, and particularly preferably 10 to 20 parts by mass, relative to 100 parts by mass of the epoxy resin (A). When the content of blocked urethane in the adhesive is (a) 1 part by mass or more per 100 parts by mass of epoxy resin (A), the resulting cured product tends to be non-brittle and have good impact peel adhesion, whereas when the content of blocked urethane is (b) 50 parts by mass or less, the resulting cured product tends to have good heat resistance and / or elastic modulus (rigidity).
[0199] (Adhesive Viscosity) The viscosity of the adhesive is not particularly limited, but is preferably 1,000,000 mPa·s or less at 50° C., more preferably 800,000 mPa·s or less at 50° C., and most preferably 600,000 mPa·s or less at 50° C. According to the above-mentioned configuration, an adhesive that is easy to handle can be provided.
[0200] (1-5. Applications of adhesives) The adhesive according to one embodiment of the present invention exhibits good adhesion to a variety of substrates, including cold-rolled steel, aluminum, fiberglass-reinforced polyester (FRP), panels of cured thermosetting resins such as epoxy resins reinforced with carbon fiber, panels of thermoplastic resin sheets reinforced with carbon fiber, sheet molding compound (SMC), ABS, PVC, polycarbonate, polypropylene, TPO, wood, and glass.
[0201] Therefore, the adhesive according to one embodiment of the present invention can be used as a cured product, a one-component adhesive, a structural adhesive, or a vehicle adhesive. That is, one embodiment of the present invention can be configured as any one of the following (1) to (4); (1) A cured product obtained by curing the adhesive according to one embodiment of the present invention; (2) A one-component adhesive using the adhesive according to one embodiment of the present invention; (3) A structural adhesive using the adhesive according to one embodiment of the present invention, or (4) An adhesive for vehicles, which uses an adhesive according to one embodiment of the present invention.
[0202] A structural adhesive using the adhesive according to one embodiment of the present invention can be used as an adhesive for structural members in, for example, automobiles, vehicles (e.g., bullet trains, trains, etc.), civil engineering, architecture, building materials, woodworking, electricity, electronics, aircraft, space industry, etc. In particular, examples of applications related to automobiles include (i) adhesion of interior materials such as ceilings, doors, and seats, (ii) automobile lighting fixtures such as lamps, and (iii) adhesion of exterior materials such as side moldings.
[0203] 2. Manufacturing method of adhesive The method for producing an adhesive according to an embodiment of the present invention has a mixing step of mixing 100 parts by mass of an epoxy resin (A), a powder containing 1 to 100 parts by mass of polymer fine particles (B) and 1 to 100 parts by mass of an uncrosslinked acrylic resin (C), wherein the polymer fine particles (B) include a rubber-containing graft copolymer having an elastomer and a graft portion graft-bonded to the elastomer, the elastomer includes one or more selected from the group consisting of a diene rubber, a (meth)acrylate rubber, and an organosiloxane rubber, and the graft portion includes a polymer containing a structural unit derived from one or more monomers selected from the group consisting of an aromatic vinyl monomer, a vinyl cyanide monomer, and a (meth)acrylate monomer as a structural unit.
[0204] Since the method for producing an adhesive according to an embodiment of the present invention has the above configuration, The method for producing an adhesive according to an embodiment of the present invention may have a powder preparation step for preparing the powder before the mixing step. According to this configuration, When the adhesive is cured to obtain a cured product, the uncrosslinked acrylic resin (C) forms a domain in the cured product. Also, the average particle diameter of the polymer fine particles (B) is preferably larger than the major axis of the domain, in other words, the major axis of the domain is preferably smaller than the average particle diameter of the polymer fine particles (B). The major axis of the domain is preferably 1 nm or more and 500 μm or less, more preferably 10 nm or more and 100 μm or less, still more preferably 10 nm or more and 10 μm or less, and most preferably 10 nm or more and 1 μm or less. When the value of the major axis of the domain is "a" and the value of the average particle diameter of the polymer fine particles (B) is "b", it is preferable that "a < b", "10 × a < b", "100 × a < b", or "1000 × a < b". According to the above configuration, the peeling mode can be made better.
[0205] Hereinafter, each step will be described. In the following, the description of the configuration described in the above [1. Adhesive] will be omitted.
[0206] (2-1. Powder preparation step) In this specification, the term "particulate material" includes both powder and granules, and means an aggregate of powder, granules, etc. In addition, when making a particular distinction, "powder" means a volume average particle diameter of 0.01 mm to 0.1 mm, and "granules" means a volume average particle diameter of 0.1 mm to 10 mm. However, the powder or granule may contain coarse particles of 10 mm or more. The "volume average particle diameter" in the range of less than 10 μm can be measured using a dynamic light scattering (DLS) particle size distribution analyzer Nanotrac WaveII-EX150 (manufactured by Microtrack Bell Co., Ltd.), and the "volume average particle diameter" in the range of 10 μm or more can be measured using a laser diffraction particle size distribution analyzer Microtrack MT3000II (manufactured by Microtrack Bell Co., Ltd.).
[0207] In the powder / granule preparation step, the method for obtaining powder / granules containing the polymer fine particles (B) and the non-crosslinked acrylic resin (C) is not particularly limited, and any known method can be used.
[0208] The polymer fine particles (B) can be obtained as an aqueous latex by emulsion polymerization, etc. In the powder preparation step, for example, (a1) a non-crosslinked acrylic resin (C) is added to an aqueous latex containing the polymer fine particles (B), (a2) the polymer fine particles (B) and the non-crosslinked acrylic resin (C) in the obtained aqueous latex are coagulated together, (a3) the obtained coagulation containing the polymer fine particles (B) and the non-crosslinked acrylic resin (C) is collected, and (a4) the collected coagulation is dried to obtain a powder containing the polymer fine particles (B) and the non-crosslinked acrylic resin (C).
[0209] The method of adding the non-crosslinked acrylic resin (C) to the aqueous latex containing the polymer fine particles (B) is not particularly limited. For example, (a) a method of directly adding the non-crosslinked acrylic resin (C) to the aqueous latex, (b) a method of separately preparing an aqueous latex containing the non-crosslinked acrylic resin (C) and then adding the aqueous latex containing the non-crosslinked acrylic resin (C) to the aqueous latex containing the polymer fine particles (B), and (c) a method of separately preparing a solution containing the non-crosslinked acrylic resin (C) and then adding the solution containing the non-crosslinked acrylic resin (C) to the aqueous latex containing the polymer fine particles (B), etc. can be mentioned. As a method of adding the non-crosslinked acrylic resin (C) to the aqueous latex, a method of separately preparing an aqueous latex containing the non-crosslinked acrylic resin (C) and then adding the aqueous latex containing the non-crosslinked acrylic resin (C) to the aqueous latex containing the polymer fine particles (B) is preferable.
[0210] The powder / granule preparation step may be in the following form: (b1) polymerizing a non-crosslinked acrylic resin (C) in an aqueous latex containing polymer fine particles (B), (b2) agglomerating the polymer fine particles (B) and the non-crosslinked acrylic resin (C) in the obtained aqueous latex, (b3) recovering the obtained aggregates containing the polymer fine particles (B) and the non-crosslinked acrylic resin (C), and (b4) drying the recovered aggregates to obtain a powder / granule containing the polymer fine particles (B) and the non-crosslinked acrylic resin (C).
[0211] The powder preparation step may include a step of obtaining an aggregate containing the polymer fine particles (B) and the non-crosslinked acrylic resin (C). The method of aggregating the polymer fine particles (B) and the non-crosslinked acrylic resin (C) in the aqueous latex is not particularly limited. For example, known methods such as a salting-out method using a salt, a method using a solvent, and a method of spraying the aqueous latex can be mentioned. Here, when the polymer fine particles (B) and the non-crosslinked acrylic resin (C) in the aqueous latex are agglomerated together, the mixture containing the aggregate containing the polymer fine particles (B) and the non-crosslinked acrylic resin (C) and the aqueous solvent is also called a slurry.
[0212] In order to obtain good blocking resistance and to disperse the polymer fine particles (B) well in the epoxy resin (A) in the obtained adhesive, it is preferable that the aggregation of the polymer fine particles (B) and the non-crosslinked acrylic resin (C) in the aqueous latex is carried out in the presence of an anti-blocking agent. In other words, it is preferable that the present powder further contains an anti-blocking agent. According to this configuration, the obtained powder has (a) excellent blocking resistance and (b) excellent dispersibility of the polymer fine particles (B) in the non-crosslinked acrylic resin (C).
[0213] Examples of the antiblocking agent include antiblocking agents made of inorganic fine particles such as silicon dioxide, titanium oxide, aluminum oxide, zirconium oxide, aluminum silicate, diatomaceous earth, zeolite, kaolin, talc, calcium carbonate, calcium phosphate, barium sulfate, and magnesium hydrosilicate; antiblocking agents made of organic fine particles; and oil-based antiblocking agents such as polyethylene wax, higher fatty acid amide, metal soap, and silicone oil. Among these, antiblocking agents made of fine particles are preferred, and antiblocking agents made of organic fine particles are more preferred. As the antiblocking agent made of organic fine particles, antiblocking agents made of organic fine particles of a polymer containing one or more monomer units selected from aromatic vinyl monomers, vinyl cyan monomers, and (meth)acrylate monomers are particularly preferred.
[0214] Antiblocking agents consisting of fine particles are generally in the form of fine particles dispersed in a liquid or in the form of colloids. The fine particles in the antiblocking agent usually have a volume average particle diameter (Mv) of 10 μm or less, preferably 0.05 μm to 10.00 μm. The content of the antiblocking agent is preferably 0.01 wt % to 5.00 wt %, more preferably 0.50 wt % to 3.00 wt %, based on the total weight (100 wt %) of the powder or granule.
[0215] The antiblocking agent and other optional components can be added as appropriate in any step in the manufacturing method of the adhesive. For example, the antiblocking agent and other optional components can be added to the polymer fine particles (B), or to the water suspension (aqueous latex) of the polymer fine particles (B) and the epoxy resin (A) before or after coagulation. The antiblocking agent and other optional components can also be added to a powder containing the polymer fine particles (B), the epoxy resin (A), or the polymer fine particles (B) and the epoxy resin (A).
[0216] The method for recovering the aggregates containing the polymer fine particles (B) and the non-crosslinked acrylic resin (C) is not particularly limited as long as it can separate the aggregates from the aqueous solvent of the slurry, and any known method can be used. Examples of the method for recovering the aggregates containing the polymer fine particles (B) and the non-crosslinked acrylic resin (C) include filtering the slurry and centrifugal dehydration of the slurry.
[0217] The method for drying the aggregate is not particularly limited, and any known method such as using a dryer can be used.
[0218] The powder / granule preparation step may be in the following form: (c1) using an aqueous latex containing only the polymer fine particles (B), the polymer fine particles (B) in the aqueous latex are aggregated, (c2) the obtained aggregates of the polymer fine particles (B) are collected, (c3) the collected aggregates of the polymer fine particles (B) are mixed with the non-crosslinked acrylic resin (C), and (c4) the obtained mixture is dried to obtain a powder containing the polymer fine particles (B) and the non-crosslinked acrylic resin (C).
[0219] The method for recovering the aggregate of the polymer fine particles (B) may be the same as the method for recovering the aggregate containing the polymer fine particles (B) and the non-crosslinked acrylic resin (C) described above. The method for mixing the recovered aggregate of the polymer fine particles (B) and the non-crosslinked acrylic resin (C) is not particularly limited. For example, a mechanical mixing method using a rotation-revolution mixer, a planetary mixer, a disperser, etc. may be mentioned.
[0220] It is preferable that the powder or granule is handled (manipulated) in a temperature environment below the glass transition temperature of the graft portion of the polymer fine particles (B) throughout the manufacturing process. In other words, the shorter the time that the aggregate and powder or granule containing the polymer fine particles (B) and the non-crosslinked acrylic resin (C) are exposed to a temperature environment equal to or higher than the glass transition temperature of the graft portion of the polymer fine particles (B) throughout the manufacturing process, the more preferable. According to this configuration, the obtained powder or granule has better dispersibility of the polymer fine particles (B) in the epoxy resin (A). As a result, the obtained powder or granule can provide an adhesive in which the polymer fine particles (B) are more uniformly dispersed in the epoxy resin (A).
[0221] In this production method, the time (period) during which the aggregates and powder containing the polymer fine particles (B) and the non-crosslinked acrylic resin (C) are exposed to a temperature environment equal to or higher than the glass transition temperature of the grafted portion of the polymer fine particles (B) can be shortened by adjusting the following temperatures: the temperature of the aqueous latex containing the polymer fine particles (B), the temperature of the aqueous latex containing the polymer fine particles (B) and the non-crosslinked acrylic resin (C) (the aqueous latex before the addition of the coagulant), the temperature of the aqueous solution of the coagulant, the temperature of the aqueous latex containing the polymer fine particles (B), the non-crosslinked acrylic resin (C) and the coagulant, the drying temperature when drying the aggregates, etc.
[0222] The temperature below the glass transition temperature of the graft portion of the polymer fine particles (B) varies depending on the composition of the graft portion, and is appropriately set depending on the composition of the graft portion. The aggregate and powder containing the polymer fine particles (B) and the non-crosslinked acrylic resin (C) are preferably handled in an environment below 90°C, more preferably below 80°C, and even more preferably below 70°C throughout the production method. That is, the above-mentioned temperatures are preferably below 90°C, more preferably below 80°C, more preferably below 70°C, more preferably below 60°C, more preferably below 50°C, and even more preferably below 40°C.
[0223] The obtained powder or granule has excellent blocking resistance. In this specification, the blocking resistance of the powder or granule can be evaluated by the force required to break a block of the powder or granule. It is preferable that the force required to break the block of the powder or granule is 30,000 Pa or less. Here, the block is obtained by placing a 6.3 kg weight on 30 g of the powder or granule contained in a cylindrical container with a diameter of 50 mm, and applying a load of 6.3 kg to the powder or granule that has been left to stand at 60° C. for 2 hours. The force (the force required to break the block of the powder or granule) is a value obtained by measurement using a rheometer.
[0224] (2-2. Mixing process) In the mixing step, a powder containing a predetermined amount of polymer fine particles (B) and a non-crosslinked acrylic resin (C) is mixed with a predetermined amount of epoxy resin (A). In addition, in the mixing step, a non-crosslinked acrylic resin (C) may be mixed with a predetermined amount of epoxy resin (A) in addition to the non-crosslinked acrylic resin (C) contained in the powder. The amount of each component to be mixed may be adjusted according to the amount of each component contained in the adhesive, which is the final product.
[0225] The method for mixing the epoxy resin (A) with the powder or granule is not particularly limited, and examples thereof include mechanical mixing methods using a planetary mixer, a planetary mixer, a disperser, or the like.
[0226] An embodiment of the present invention may have the following configuration.
[0227] [1] An adhesive comprising an epoxy resin (A), and 1 to 100 parts by mass of polymer fine particles (B) and 1 to 100 parts by mass of a non-crosslinked acrylic resin (C) relative to 100 parts by mass of the epoxy resin (A), the polymer fine particles (B) comprising a rubber-containing graft copolymer having an elastomer and a graft portion graft-bonded to the elastomer, the elastomer comprising at least one rubber selected from the group consisting of a diene rubber, a (meth)acrylate rubber, and an organosiloxane rubber, the graft portion comprising a polymer comprising, as a constituent unit, a constituent unit derived from at least one monomer selected from the group consisting of an aromatic vinyl monomer, a vinyl cyan monomer, and a (meth)acrylate monomer, the adhesive being such that, when the adhesive is cured to obtain a cured product, the non-crosslinked acrylic resin (C) forms domains in the cured product, and the average particle diameter of the polymer fine particles (B) is greater than the major axis of the domains.
[0228] [2] The adhesive according to [1], wherein the polymer fine particles (B) account for 50 to 99% by weight and the non-crosslinked acrylic resin (C) accounts for 1 to 50% by weight, assuming that the total of the polymer fine particles (B) and the non-crosslinked acrylic resin (C) is 100% by weight.
[0229] [3] The adhesive according to [1] or [2], wherein the weight average molecular weight of the non-crosslinked acrylic resin (C) is 100,000 or less.
[0230] [4] The adhesive according to any one of [1] to [3], wherein the non-crosslinked acrylic resin (C) has a glass transition temperature of 80° C. or lower.
[0231] [5] The adhesive according to any one of [1] to [4], wherein the non-crosslinked acrylic resin (C) is a liquid having a viscosity of 1,000,000 mPa·s or less at 25° C.
[0232] [6] A method for producing an adhesive, comprising a mixing step of mixing 100 parts by mass of an epoxy resin (A) with a powder or granule containing 1 to 100 parts by mass of polymer fine particles (B) and 1 to 100 parts by mass of a non-crosslinked acrylic resin (C), wherein the polymer fine particles (B) contain a rubber-containing graft copolymer having an elastomer and a graft portion graft-bonded to the elastomer, the elastomer containing one or more rubbers selected from the group consisting of diene rubbers, (meth)acrylate rubbers, and organosiloxane rubbers, and the graft portion contains a polymer containing, as a constituent unit, a constituent unit derived from one or more monomers selected from the group consisting of aromatic vinyl monomers, vinyl cyan monomers, and (meth)acrylate monomers.
[0233] [7] The method for producing an adhesive according to [6], wherein when the adhesive is cured to obtain a cured product, the non-crosslinked acrylic resin (C) forms a domain in the cured product.
[0234] [8] The method for producing an adhesive according to [7], wherein the average particle size of the polymer fine particles (B) is larger than the major axis of the domains.
[0235] [9] A method for producing an adhesive as described in any one of [6] to [8], wherein the force required to break the powder / granule block is 30,000 Pa or less: the block is obtained by placing a 6.3 kg weight on 30 g of the powder / granule contained in a cylindrical container having a diameter of 50 mm, and applying a load of 6.3 kg to the powder / granule that has been allowed to stand at 60°C for 2 hours, and the force is a value obtained by measurement using a rheometer. EXAMPLES
[0236] [1. Details of each ingredient] <Epoxy resin (A)> A-1: Epoxy resin, manufactured by Mitsubishi Chemical Corporation, product name "JER828EL".
[0237] <Preparation of polymer fine particles (B)> (Production Example 1-1: Preparation of aqueous latex (L-1) containing polymer fine particles (B-1)) Into the pressure-resistant polymerization vessel, 160 parts by weight of deionized water, 0.002 parts by weight of disodium ethylenediaminetetraacetate (EDTA), 0.001 parts by weight of ferrous sulfate heptahydrate, 0.029 parts by weight of polyoxyethylene lauryl ether phosphate, and 0.003 parts by weight of sodium hydroxide were charged. Here, in the presence of sodium hydroxide, polyoxyethylene lauryl ether phosphate became sodium polyoxyethylene lauryl ether phosphate, which functioned as an emulsifier. Next, while stirring the charged raw materials, the gas inside the pressure-resistant polymerization vessel was replaced with nitrogen, thereby thoroughly removing oxygen from inside the pressure-resistant polymerization vessel. Then, 76.5 parts by weight of butadiene (Bd) and 23.5 parts by weight of styrene (St) were charged into the pressure-resistant polymerization vessel, and the temperature inside the pressure-resistant polymerization vessel was raised to 45°C. Then, 0.03 parts by weight of paramenthane hydroperoxide (PHP) was added to the pressure-resistant polymerization vessel, followed by 0.05 parts by weight of sodium formaldehyde sulfoxylate (SFS) to start polymerization. At 20 hours after the start of polymerization, the polymerization was terminated by removing the remaining monomers that were not used in the polymerization by volatilization under reduced pressure. During the polymerization, PHP, polyoxyethylene lauryl ether phosphate, and sodium hydroxide were each added to the pressure-resistant polymerization vessel in an arbitrary amount and at an arbitrary time. By this polymerization, an aqueous latex (R-1) containing an elastomer mainly composed of polystyrene-butadiene rubber was obtained. The volume average particle size of the elastomer contained in the obtained aqueous latex was 192 nm.
[0238] A glass reactor was charged with 215 parts by weight of an aqueous polystyrene-butadiene rubber latex (R-1) (containing 70 parts by weight of an elastomer mainly composed of polystyrene-butadiene rubber) and 82 parts by weight of deionized water. Here, the glass reactor had a thermometer, a stirrer, a reflux condenser, a nitrogen inlet, and a monomer addition device. The raw materials charged at 60°C were stirred while the gas in the glass reactor was replaced with nitrogen. Next, 2.6 parts by weight of 1,3-butylene glycol dimethacrylate and 0.07 parts by weight of t-butyl hydroperoxide (BHP) were added to the glass reactor, and the mixture in the glass reactor was stirred for 10 minutes. Then, 0.004 parts by weight of EDTA, 0.001 parts by weight of ferrous sulfate heptahydrate, and 0.13 parts by weight of SFS were added to the glass reactor, and the mixture in the glass reactor was stirred for 30 minutes. Then, 0.013 parts by weight of BHP was added to the glass reactor, and the mixture in the glass reactor was stirred for another 30 minutes. Then, a mixture of 28.5 parts by weight of methyl methacrylate (MMA), 1.5 parts by weight of butyl acrylate (BA), and 0.085 parts by weight of BHP was continuously added to the glass reactor over 120 minutes. Then, 0.013 parts by weight of BHP was added to the glass reactor, and the mixture in the glass reactor was stirred for another hour to complete the polymerization. By the above operations, an aqueous latex (L-1) containing polymer fine particles (B-1) was obtained. The polymerization conversion rate of the monomer components was 99% or more. The volume average particle diameter of the polymer fine particles (B) contained in the obtained aqueous latex was 200 nm.
[0239] (Measurement of volume average particle size) The volume average particle size (Mv) of the elastomer or polymer fine particles (B) dispersed in the aqueous latex was measured using Nanotrac WaveII-EX150 (manufactured by Microtrackbell Co., Ltd.). The aqueous latex was diluted with deionized water and used as the measurement sample. The measurement was performed by inputting the refractive index of water and the elastomer or polymer fine particles (B) obtained in each production example, and adjusting the sample concentration so that the measurement time was 120 seconds and the loading index was within the range of 1 to 10.
[0240] The volume average particle diameter (Mv) of the powder was measured using a laser diffraction particle size distribution analyzer Microtrac MT3000II (manufactured by Microtrac Bell Co., Ltd.). The powder was dispersed in water to obtain a dispersion liquid, which was used as a sample. The powder used in the examples all had a volume average particle diameter of 10 mm or less.
[0241] <Non-crosslinked acrylic resin (C)> C-1: Non-crosslinked butyl acrylate homopolymer (BA 100% by weight, Tg: -50.5°C, Mw: 13,000, viscosity at 25°C: 58,000 mPa·s), C-2: Non-crosslinked butyl acrylate homopolymer (BA 100% by weight, Tg: -52.5°C, Mw: 8,500, viscosity at 25°C: 27,000 mPa·s), C-3: Non-crosslinked butyl acrylate homopolymer (BA 100% by weight, Tg: -48.1°C, Mw: 25,000, viscosity at 25°C: 133,000 mPa·s), C-4: Non-crosslinked butyl acrylate homopolymer (BA 100% by weight, Tg: -46.5°C, Mw: 40,000, viscosity at 25°C: 441,000 mPa·s), and C-5: Non-crosslinked butyl acrylate / methyl methacrylate copolymer (50% by weight of BA and 50% by weight of MMA, Tg: 45° C., Mw: 20,000, viscosity at 25° C.: could not be measured because it was a solid). The method for preparing each of the non-crosslinked acrylic resins (C) and the aqueous latexes containing each of the non-crosslinked acrylic resins (C) is as follows.
[0242] <Preparation of Non-Crosslinked Acrylic Resin (C)> (Production Example 2-1: Preparation of Water-Based Latex (FP-1) Containing Non-Crosslinked Acrylic Resin (C-1)) Into a glass reactor having a thermometer, a stirrer, a reflux condenser, a nitrogen inlet, and a monomer component addition device, 220 parts by weight of deionized water, 0.9 parts by weight of polyoxyethylene lauryl ether phosphate, and 0.1 parts by weight of sodium hydroxide were added. Here, in the presence of sodium hydroxide, polyoxyethylene lauryl ether phosphate became sodium polyoxyethylene lauryl ether phosphate, which functioned as an emulsifier. Next, while stirring the raw materials charged at 68°C, the gas inside the glass reactor was replaced with nitrogen, thereby sufficiently removing oxygen from inside the glass reactor. Then, a mixture of 100 parts by weight of BA, 3.0 parts by weight of 2-ethylhexyl thioglycolate, and 1.0 parts by weight of BHP was continuously added into the glass reactor over a period of 300 minutes. Then, 0.05 parts by weight of BHP was added into the glass reactor, and the mixture in the glass reactor was further stirred for 1 hour to complete the polymerization. By the above operations, an aqueous emulsion (aqueous latex) (FP-1) containing 100% by weight of butyl acrylate homopolymer as the non-crosslinked acrylic resin (C-1) was obtained. The polymerization conversion rate of the monomer components was 99% or more. The volume average particle diameter of the non-crosslinked acrylic resin (C) contained in the obtained aqueous latex was 80 nm. The solid content concentration (concentration of the non-crosslinked acrylic resin (C)) in the obtained aqueous latex (FP-1) 100% by weight was 33% by weight.
[0243] (Production Example 2-2: Preparation of Water-Based Latex (FP-2) Containing Non-Crosslinked Acrylic Resin (C-2)) An aqueous emulsion (aqueous latex) (FP-2) containing 100% by weight of butyl acrylate homopolymer was obtained as the non-crosslinked acrylic resin (C-2) in the same manner as in Production Example 2-1, except that the amount of 2-ethylhexyl thioglycolate in the production process of the non-crosslinked acrylic resin (C) (FP-1) was changed to 5.0 parts by weight.
[0244] (Production Example 2-3: Preparation of Water-Based Latex (FP-3) Containing Non-Crosslinked Acrylic Resin (C-3)) An aqueous emulsion (aqueous latex) (FP-3) containing 100% by weight of butyl acrylate homopolymer was obtained as the non-crosslinked acrylic resin (C-3) by the same method as in Production Example 2-1, except that the amount of 2-ethylhexyl thioglycolate in the production process of the non-crosslinked acrylic resin (C) (FP-1) was changed to 1.5 parts by weight.
[0245] (Production Example 2-4: Preparation of Water-Based Latex (FP-4) Containing Non-Crosslinked Acrylic Resin (C-4)) An aqueous emulsion (aqueous latex) (FP-4) containing 100% by weight of butyl acrylate homopolymer was obtained as the non-crosslinked acrylic resin (C-4) by the same method as in Production Example 2-1, except that the amount of 2-ethylhexyl thioglycolate in the production process of the non-crosslinked acrylic resin (C) (FP-1) was changed to 0.75 parts by weight.
[0246] (Production Example 2-5: Preparation of Water-Based Latex (FP-5) Containing Non-Crosslinked Acrylic Resin (C-5)) An aqueous emulsion (aqueous latex) (FP-5) containing a copolymer of 50% by weight of butyl acrylate and 50% by weight of methyl methacrylate (non-crosslinked butyl acrylate / methyl methacrylate copolymer) as the non-crosslinked acrylic resin (C-5) was obtained in the same manner as in Production Example 2-1, except that in the production process of the non-crosslinked acrylic resin (C) (FP-1), 100 parts by weight of BA was changed to 50 parts by weight of MMA and 50 parts by weight of BA.
[0247] <Preparation of polymer particles having a crosslinked polymer layer> Into a glass reactor equipped with a thermometer, a stirrer, a reflux condenser, a nitrogen inlet, and an addition device for monomer components and an emulsifier, 182 parts by mass of deionized water, 0.006 parts by mass of EDTA, 0.0015 parts by mass of ferrous sulfate heptahydrate, 0.2 parts by mass of SFS, and 0.3 parts by mass of sodium dodecylbenzenesulfonate (SDBS) were charged. The temperature inside the glass reactor was raised to 60°C while stirring the charged raw materials in a nitrogen stream. Next, a mixture of 83 parts by mass of BA, 0.17 parts by mass of allyl methacrylate (ALMA), and 0.024 parts by mass of CHP was continuously dropped into the glass reactor over a period of 200 minutes. The mixture in the glass reactor was stirred for 0.5 hours after the end of the addition of the mixture to complete the polymerization, and an aqueous latex (R-2) containing a crosslinked polymer layer of polymer particles was obtained. Subsequently, a mixture of 16.15 parts by mass of MMA, 0.85 parts by mass of BA, and 0.05 parts by mass of CHP was continuously added to the glass reactor over 50 minutes. After the addition was completed, 0.04 parts by mass of CHP was added to the glass reactor, and the mixture in the glass reactor was stirred for another hour to complete the polymerization, thereby obtaining an aqueous latex (CP-1) containing polymer microparticles having a crosslinked polymer layer. The polymerization conversion rate of the monomer components was 99% or more. The volume average particle diameter of the polymer microparticles contained in the obtained aqueous latex was 100 nm. The solid content concentration (concentration of polymer microparticles) in 100% by weight of the obtained aqueous latex (CP-1) was 35% by weight.
[0248] <Preparation of powder and granules> (Production Example 3-1: Preparation of Powder (P-1)) (i) Water, (ii) 67 parts by weight of epoxidized soybean oil (ADEKA Corporation, Adeka Cizer O-130P) and 33 parts by weight of triethylene glycol bis[3-(-t-butyl-4-hydroxy-5-methylphenyl)propionate] (Irganox 245, BASF Japan Ltd.), and (iii) SDBS as an emulsifier were mixed together using a homogenizer to prepare an aqueous emulsion (S-1) (50% content of mixture of epoxidized soybean oil and triethylene glycol bis[3-(-t-butyl-4-hydroxy-5-methylphenyl)propionate]. In addition, 4 parts by weight of calcium acetate was dissolved in ion-exchanged water adjusted to 70°C, and 600 parts by weight of the water was prepared. Next, 325 parts by weight of the aqueous latex (L-1) corresponding to 100 parts by weight of the polymer fine particles (B) and 22.2 parts by weight of the aqueous emulsion (S-1) (corresponding to 11.1 parts by weight of a mixture of epoxidized soybean oil and triethylene glycol bis[3-(-t-butyl-4-hydroxy-5-methylphenyl)propionate]) were added to 600 parts by weight of the ion-exchanged water to obtain a slurry containing a coagulated product containing the polymer fine particles (B). Next, the slurry was centrifuged to obtain a wet powder, which was the coagulated product. Furthermore, using the obtained wet powder, a total of two cycles were repeated, including an operation of adding the wet powder to 500 parts by weight of ion-exchanged water and an operation of centrifuging the obtained mixture, to obtain a washed wet powder. Finally, the wet powder was dried in a dryer at 50 ° C. for 48 hours to obtain a powder (P-1) containing the polymer fine particles (B). The concentration of the polymer fine particles (B) in the resulting powder (P-1) (100% by weight) was 90% by weight.
[0249] (Production Example 3-2: Preparation of Powder (P-2)) 333 parts by weight of aqueous latex (L-1) equivalent to 100 parts by weight of polymer fine particles (B), 75.8 parts by weight of the aqueous emulsion (aqueous latex) (FP-1) (equivalent to 25 parts by weight of non-crosslinked acrylic resin (C)), and 1.1 parts by weight of Irganox 1135 were mixed to obtain an aqueous latex, which was dissolved with 4 parts of calcium chloride and poured into 600 parts of ion-exchanged water adjusted to 70°C, to coagulate the polymer fine particles (B) and the non-crosslinked acrylic resin (C), and obtain a slurry containing a coagulated material containing the polymer fine particles (B) and the non-crosslinked acrylic resin (C). The obtained slurry was then centrifuged to obtain a wet powder that was a coagulated material containing the polymer fine particles (B) and the non-crosslinked acrylic resin (C). Furthermore, the obtained wet powder was subjected to a total of two cycles of an operation of pouring the wet powder into 500 parts of ion-exchanged water and an operation of centrifuging the obtained mixture to obtain a washed wet powder. Finally, the wet powder was dried in a dryer at 50°C for 48 hours to obtain a powder (P-2) containing polymer fine particles (B) and non-crosslinked acrylic resin (C). The concentration of polymer fine particles (B) in 100% by weight of the obtained powder (P-2) was 79% by weight, and the concentration of non-crosslinked acrylic resin (C) was 20%.
[0250] (Production Example 3-3: Preparation of Powder (P-3)) A powder (P-3) containing polymer fine particles (B) and non-crosslinked acrylic resin (C) was obtained in the same manner as in Production Example 3-2, except that the aqueous latex (FP-1) was changed to aqueous latex (FP-2) as the non-crosslinked acrylic resin (C) in Production Example 3-2. The concentration of the polymer fine particles (B) in 100% by weight of the obtained powder (P-3) was 79% by weight, and the concentration of the non-crosslinked acrylic resin (C) was 20%.
[0251] (Production Example 3-4: Preparation of Powder (P-4)) In Production Example 3-2, except that the aqueous latex (FP-1) was changed to the aqueous latex (FP-3) as the non-crosslinked acrylic resin (C), a powder (P-4) containing polymer fine particles (B) and non-crosslinked acrylic resin (C) was obtained in the same manner as in Production Example 3-2. The concentration of the polymer fine particles (B) in 100% by weight of the obtained powder (P-4) was 79% by weight, and the concentration of the non-crosslinked acrylic resin (C) was 20%.
[0252] (Production Example 3-5: Preparation of Powder (P-5)) A powder (P-5) containing polymer fine particles (B) and non-crosslinked acrylic resin (C) was obtained in the same manner as in Production Example 3-2, except that the aqueous latex (FP-1) was changed to aqueous latex (FP-4) as the non-crosslinked acrylic resin (C) in Production Example 3-2. The concentration of the polymer fine particles (B) in 100% by weight of the obtained powder (P-5) was 79% by weight, and the concentration of the non-crosslinked acrylic resin (C) was 20%.
[0253] (Production Example 3-6: Preparation of Powder (P-6)) In Production Example 3-2, except that the aqueous latex (FP-1) was changed to the aqueous latex (FP-5) as the non-crosslinked acrylic resin (C), a powder (P-6) containing polymer fine particles (B) and non-crosslinked acrylic resin (C) was obtained by the same method as in Production Example 3-2. The concentration of the polymer fine particles (B) in the obtained powder (P-6) (100% by weight) was 79% by weight, and the concentration of the non-crosslinked acrylic resin (C) was 20%.
[0254] (Production Example 3-7; Preparation of Powder (P-7)) 266 parts by weight of aqueous latex (L-1) equivalent to 80 parts by weight of polymer fine particles (B), 57.1 parts by weight of the aqueous emulsion (CP-1) (equivalent to 20 parts by weight of polymer fine particles having a crosslinked polymer layer), and 22.2 parts by weight of the aqueous emulsion (S-1) (equivalent to 11.1 parts by weight of resin (epoxidized soybean oil)) were mixed. The obtained aqueous latex was poured into 600 parts of ion-exchanged water in which 4 parts of calcium chloride had been dissolved and adjusted to 70 ° C., and the polymer fine particles (B) and the polymer fine particles having a crosslinked polymer layer were coagulated to obtain a slurry containing a coagulated product containing polymer fine particles (B) and polymer fine particles having a crosslinked polymer layer. Thereafter, the obtained slurry was centrifuged to obtain a wet powder which was the coagulated product. Furthermore, for the obtained wet powder, an operation of pouring the wet powder into 500 parts of ion-exchanged water and an operation of centrifuging the obtained mixture were repeated for a total of two cycles to obtain a washed wet powder. Finally, the wet powder was dried in a dryer at 50°C for 48 hours to obtain a powder (P-7) containing polymer fine particles (B) and polymer fine particles having a crosslinked polymer layer. The concentration of polymer fine particles (B) in the obtained powder (P-7) (100% by weight) was 72% by weight, and the concentration of polymer fine particles having a crosslinked polymer layer was 18%.
[0255] (Blocking resistance of powder particles) The obtained powder was used to prepare a powder block by carrying out the following steps (1) to (3) in order: (1) 30 g of powder was placed in a cylindrical container with a diameter of 50 mm; (2) a 6.3 kg weight was placed on the powder in the container, and the powder was allowed to stand at 60°C for 2 hours, and a load of 6.3 kg was applied to the powder to obtain a block; (3) the obtained block was removed from the container. Next, the force required to break the obtained block of powder was measured using a rheometer. Based on the obtained results, the blocking resistance was evaluated according to the following criteria. All of the powders used in the examples were "passed." Pass: The force required to break the powder block is 30,000 Pa or less. Fail: The force required to break the block of powder exceeds 30,000 Pa.
[0256] <Preparation of adhesive (thermosetting resin composition)> Comparative Example 1: (Production Example 4-1; Preparation of Adhesive (Thermosetting Resin Composition)) To 100 parts by weight of JER828EL, which is an epoxy resin (A-1), 10 parts by weight of "Cardura E10P" (trade name, manufactured by Momentive) as a reactive diluent, 7 parts by weight of dicyandiamide "jER Cure Dicy7" (trade name, manufactured by Mitsubishi Chemical Corporation) as a curing agent, 1 part by weight of aromatic dimethylurea "Dyhard UR300" (trade name, manufactured by Degussa) as a curing accelerator, 5 parts by weight of silica "CAB-O-SIL TS720" (trade name, manufactured by CABOT Corporation), 0.3 parts by weight of carbon black "Monarch280" (trade name, manufactured by CABOT Corporation), 15 parts by weight of calcium carbonate "Whiten SB" (trade name, manufactured by Shiraishi Calcium Co., Ltd.), and 1.5 parts by weight of calcium oxide "CML#31" (trade name, manufactured by Omi Chemical Industry Co., Ltd.) were added, and the mixture was mixed for 10 minutes at 2000 rpm in a centrifugal mixer to obtain an adhesive.
[0257] Comparative Example 2: (Production Example 4-2; Preparation of adhesive (thermosetting resin composition)) 33.3 parts by weight of the powder (P-1) and 100 parts by weight of JER828EL, which is the epoxy resin (A-1), were weighed and mixed in a planetary centrifugal mixer at 2000 rpm for 30 minutes to obtain a resin composition. To the resin composition, 10 parts by weight of "Cardura E10P" (manufactured by Momentive) as a reactive diluent, 7 parts by weight of dicyandiamide "jER Cure Dicy7" (manufactured by Mitsubishi Chemical Corporation) as a curing agent, 1 part by weight of aromatic dimethylurea "Dyhard UR300" (manufactured by Degussa) as a curing accelerator, 5 parts by weight of silica "CAB-O-SIL TS720" (manufactured by CABOT), 0.3 parts by weight of carbon black "Monarch280" (manufactured by CABOT), 15 parts by weight of calcium carbonate "Whiten SB" (manufactured by Shiraishi Calcium Co., Ltd.), and 1.5 parts by weight of calcium oxide "CML#31" (manufactured by Omi Chemical Industry Co., Ltd.) were added, and the mixture was mixed for 10 minutes at 2000 rpm in a planetary centrifugal mixer to obtain an adhesive.
[0258] Example 1: (Production Example 4-3; Preparation of adhesive (thermosetting resin composition)) 37.5 parts by weight of the powder (P-2) and 100 parts by weight of JER828EL, which is the epoxy resin (A-1), were weighed and mixed in a planetary centrifugal mixer at 2000 rpm for 30 minutes to obtain an adhesive (resin composition). To the adhesive, 10 parts by weight of "Cardura E10P" (manufactured by Momentive) as a reactive diluent, 7 parts by weight of dicyandiamide "jER Cure Dicy7" (manufactured by Mitsubishi Chemical Corporation) as a curing agent, 1 part by weight of aromatic dimethylurea "Dyhard UR300" (manufactured by Degussa) as a curing accelerator, 5 parts by weight of silica "CAB-O-SIL TS720" (manufactured by CABOT), 0.3 parts by weight of carbon black "Monarch280" (manufactured by CABOT), 15 parts by weight of calcium carbonate "Whiten SB" (manufactured by Shiraishi Calcium Co., Ltd.), and 1.5 parts by weight of calcium oxide "CML#31" (manufactured by Omi Chemical Industry Co., Ltd.) were added, and the mixture was mixed for 10 minutes at 2000 rpm in a planetary centrifugal mixer to obtain a one-component adhesive.
[0259] Example 2: (Production Example 4-4; Preparation of adhesive (thermosetting resin composition)) A one-component adhesive was obtained in the same manner as in Production Example 4-3, except that the powder particles were changed to (P-3).
[0260] Example 3: (Production Example 4-5; Preparation of adhesive (thermosetting resin composition)) A one-component adhesive was obtained in the same manner as in Production Example 4-3, except that the powder particles were changed to (P-4).
[0261] Example 4: (Production Example 4-6; Preparation of adhesive (thermosetting resin composition)) A one-component adhesive was obtained in the same manner as in Production Example 4-3, except that the powder particles were changed to (P-5).
[0262] Example 5: (Production Example 4-7; Preparation of adhesive (thermosetting resin composition)) A one-component adhesive was obtained in the same manner as in Production Example 4-3, except that the powder particles were changed to (P-6).
[0263] Comparative Example 3: (Production Example 4-8; Preparation of adhesive (thermosetting resin composition)) 41.7 parts by weight of the powder (P-7) and 100 parts by weight of JER828EL, which is the epoxy resin (A-1), were weighed and mixed in a planetary centrifugal mixer at 2000 rpm for 30 minutes to obtain a resin composition. To the resin composition, 10 parts by weight of "Cardura E10P" (manufactured by Momentive) as a reactive diluent, 7 parts by weight of dicyandiamide "jER Cure Dicy7" (manufactured by Mitsubishi Chemical Corporation) as a curing agent, 1 part by weight of aromatic dimethylurea "Dyhard UR300" (manufactured by Degussa) as a curing accelerator, 5 parts by weight of silica "CAB-O-SIL TS720" (manufactured by CABOT), 0.3 parts by weight of carbon black "Monarch280" (manufactured by CABOT), 15 parts by weight of calcium carbonate "Whiten SB" (manufactured by Shiraishi Calcium Co., Ltd.), and 1.5 parts by weight of calcium oxide "CML#31" (manufactured by Omi Chemical Industry Co., Ltd.) were added, and the mixture was mixed for 10 minutes at 2000 rpm in a planetary centrifugal mixer to obtain an adhesive.
[0264] Comparative Example 4: (Production Example 4-9; Preparation of Adhesive (Thermosetting Resin Composition)) An adhesive was obtained in the same manner as in Production Example 4-2, except that the amount of silica "CAB-O-SIL TS720" (product name, manufactured by CABOT) was changed to 12.5 parts by weight.
[0265] [2. Major axis of the domain] The adhesives obtained in Examples 1 to 5 were cured under the conditions of 170°C x 30 minutes. Next, the domains formed by the non-crosslinked acrylic resin (C) present in the cured product were observed by SEM observation, and the major axis of the domains was calculated. The proportion of the domains present was calculated by image analysis. For example, FIG. 1 is an SEM image of the cured product of the adhesive of Example 3. In the SEM image, "10" indicates the polymer fine particles (B) (see the gray, roughly spherical substance present at the tip of the arrow in FIG. 1), and "20" indicates the domain of the non-crosslinked acrylic resin (C) (see the white, roughly spherical substance present at the tip of the arrow in FIG. 1).
[0266] In Examples 1 to 5, the major axis of the domains formed by the non-crosslinked acrylic resin (C) was 40 nm in each case. As is clear from Fig. 1, the average particle size of the polymer fine particles (B) was larger than the major axis of the domains.
[0267] 3. Evaluation of T-peel adhesion strength and peeling mode The adhesive was applied to two SPCC steel plates with dimensions of 25 x 200 x 0.5 mm, the SPCC steel plates were overlapped so that the adhesive layer was 0.25 mm thick, and the adhesive was cured at 170°C for 1 hour to obtain a bonded steel plate. The T-peel adhesive strength of the obtained bonded steel plate was measured at 23°C according to JIS K6854. The fracture surface of the test piece after the measurement was visually evaluated.
[0268] 4. Evaluation of peeling pattern The peeling mode of the adhesive was evaluated by visually observing the fracture surface of the test piece after measuring the T-peel adhesive strength.
[0269] <Evaluation criteria> CF100: The peel mode is cohesive failure.
[0270] AF100: The peeling mode is interfacial failure.
[0271] 5. Viscosity Evaluation The viscosity of the adhesive was measured using a digital viscometer DV-II+Pro manufactured by BROOKFIELD Corp. Using a spindle appropriate for the viscosity range, the viscosity of the adhesive was measured at a measurement temperature of 25°C while changing the shear rate as necessary.
[0272] Table 1 below shows the composition and amount of each adhesive, and Table 2 shows the evaluation results of each adhesive. [Table 1]
[0273] [Table 2] 6. Test Results As shown in Table 2, it was revealed that the adhesives according to one embodiment of the present invention obtained in Examples 1 to 5 were excellent in all of the peeling mode, adhesive strength, and viscosity. It was also revealed that the lower the glass transition temperature (Tg) of the polymer fine particles (B), the lower the viscosity of the adhesive.
[0274] As described above, the adhesives obtained in Examples 1 to 5 were one-component adhesives. As shown in Table 2, the one-component adhesives obtained in Examples 1 to 5 were good in all of the peeling mode, adhesive strength, and viscosity. Therefore, it was found that the adhesive according to one embodiment of the present invention can be suitably used as a one-component adhesive. [Industrial Applicability]
[0275] The present invention can be widely used in the field of adhesives. [Explanation of symbols]
[0276] 10 Polymer fine particles (B) 20 Domain of non-crosslinked acrylic resin (C)
Claims
1. The composition comprises an epoxy resin (A), and, relative to 100 parts by mass of the epoxy resin (A), 1 to 50 parts by mass of polymer fine particles (B) and 1 to 20 parts by mass of a non-crosslinked acrylic resin (C), the polymer fine particles (B) contain a rubber-containing graft copolymer having an elastomer and a graft portion graft-bonded to the elastomer, the elastic body includes at least one rubber selected from the group consisting of diene-based rubbers, (meth)acrylate-based rubbers, and organosiloxane-based rubbers, the graft portion is an adhesive comprising a polymer including, as a structural unit, a structural unit derived from one or more monomers selected from the group consisting of an aromatic vinyl monomer, a vinyl cyan monomer, and a (meth)acrylate monomer; The adhesive is one in which, when cured to obtain a cured product, the non-crosslinked acrylic resin (C) forms a domain in the cured product, The average particle size of the polymer fine particles (B) is larger than the major axis of the domains, The domain refers to the non-crosslinked acrylic resin (C) in a particle state, The adhesive, in which the polymer fine particles (B) account for 50 to 99% by weight and the non-crosslinked acrylic resin (C) account for 1 to 50% by weight, when the total of the polymer fine particles (B) and the non-crosslinked acrylic resin (C) is 100% by weight.
2. 2. The adhesive according to claim 1, wherein the non-crosslinked acrylic resin (C) has a weight average molecular weight of 50,000 or less.
3. 3. The adhesive according to claim 1 or 2, wherein the non-crosslinked acrylic resin (C) has a glass transition temperature of 80° C. or lower.
4. The adhesive according to any one of claims 1 to 3, wherein the non-crosslinked acrylic resin (C) is a liquid having a viscosity of 1,000,000 mPa·s or less at 25°C.
5. The method includes a mixing step of mixing 100 parts by mass of an epoxy resin (A) with a powder or granular material containing 1 to 50 parts by mass of polymer fine particles (B) and 1 to 20 parts by mass of a non-crosslinked acrylic resin (C), the polymer fine particles (B) contain a rubber-containing graft copolymer having an elastomer and a graft portion graft-bonded to the elastomer, the elastic body includes at least one rubber selected from the group consisting of diene-based rubbers, (meth)acrylate-based rubbers, and organosiloxane-based rubbers, the graft portion includes a polymer including, as a structural unit, a structural unit derived from one or more monomers selected from the group consisting of an aromatic vinyl monomer, a vinyl cyan monomer, and a (meth)acrylate monomer; The method for producing an adhesive, wherein the polymer fine particles (B) are 50 to 99% by weight and the non-crosslinked acrylic resin (C) is 1 to 50% by weight, when the total of the polymer fine particles (B) and the non-crosslinked acrylic resin (C) is 100% by weight.
6. Prior to the mixing step, the mixture contains 1 to 50 parts by mass of the polymer fine particles (B) and 1 to 20 parts by mass of the non-crosslinked acrylic resin (C), 6. The method for producing an adhesive according to claim 5, further comprising a powder / grain preparation step of preparing the powder / grain containing 50 to 99% by weight of the polymer fine particles (B) and 1 to 50% by weight of the non-crosslinked acrylic resin (C), where the total of the polymer fine particles (B) and the non-crosslinked acrylic resin (C) is taken as 100% by weight.
7. The adhesive is one in which, when cured to obtain a cured product, the non-crosslinked acrylic resin (C) forms a domain in the cured product, The method for producing an adhesive according to claim 5 or 6, wherein the domains are formed by the non-crosslinked acrylic resin (C) being in a particulate state.
8. The method for producing an adhesive according to claim 7 , wherein the average particle size of the polymer fine particles (B) is larger than the major axis of the domains.
9. The method for producing an adhesive according to any one of claims 6 to 8, wherein a force required to break the powder / granule block is 30,000 Pa or less: Here, the block is obtained by placing a weight of 6.3 kg on 30 g of the powder or grain contained in a cylindrical container having a diameter of 50 mm, and allowing the powder or grain to stand at 60° C. for 2 hours, and applying a load of 6.3 kg to the powder or grain. The force is a value obtained by measurement using a rheometer.
Citation Information
Patent Citations
Storable and rapidly curable epoxy resin adhesives* and coated fiber web* woven fabric* thick plate or sheet using same
JP1978085831A
Dispersion of cross-linked rubber particles, dispersed particles and curing type adhesive composition
JP1999060818A
Epoxy resin composition
JP2010180351A
Polymer fine particle-containing curable resin composition improved in storage stability and adhesion
JP2016199739A
Polymer fine particle-containing curable composition excellent in mechanical strength
JP2018053026A